Pellet, molded product and method for producing molded product

JP2025026328APending Publication Date: 2025-02-21ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024105708
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-08
Filing Date
2024-06-28
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、色調と蛍光強度を改善させた、主鎖にN-置換マレイミド単量体由来の構造単位を含むメタクリル系樹脂を含むメタクリル系樹脂組成物からなるペレット、成形体及び成形体の製造方法を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026328000013
    Figure 2025026328000013
  • Figure 2025026328000001
    Figure 2025026328000001
  • Figure 2025026328000002
    Figure 2025026328000002
Patent Text Reader

Abstract

To provide a pellet composed of a methacrylic resin composition containing a methacrylic resin with structural units derived from N-substituted maleimide monomers in its main chain, featuring enhanced color tone and fluorescence intensity, and a molded product.SOLUTION: The present invention provides a pellet composed of a methacrylic resin composition containing a methacrylic resin with structural units (X) derived from N-substituted maleimide monomers in its main chain, the pellet containing less than 0.30 mass ppm of 2-amino-N-substituted maleimide.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pellet, a compact, and a method for producing the compact. [Background technology]

[0002] Traditionally, glass has been used for optical components such as lenses and prisms, but in recent years, plastics have come to be used in response to the need for greater design freedom, such as for lighter and smaller lenses and aspheric lenses. Generally, methacrylic resins, styrene resins, polycarbonates, cyclic olefin resins, etc. are known plastics used for optical components.

[0003] In general, plastics are prone to birefringence due to orientation associated with molding processing, which adversely affects imaging performance when used as optical components. Furthermore, when injection molding, which has high productivity, is used as a molding method, greater orientation is likely to occur, and the impact on imaging performance becomes more pronounced. Methacrylic resins, such as polymethyl methacrylate, are highly transparent and have low intrinsic birefringence, which allows for relatively low orientation birefringence, and have been used favorably as optical components. However, as higher optical performance is now required, materials that can reduce orientation birefringence are in demand.

[0004] For example, Patent Documents 1 and 2 disclose that the orientation birefringence and photoelastic birefringence can be reduced by a copolymer obtained by copolymerizing monomers including methyl methacrylate, 2,2,2-trifluoroethyl methacrylate, and benzyl methacrylate. This is based on the idea of ​​selecting multiple monomers with different signs of intrinsic birefringence and photoelastic coefficient when made into homopolymers, combining and copolymerizing them to adjust the composition, thereby reducing the orientation birefringence and photoelastic birefringence as a copolymer. However, since this copolymer has a low glass transition temperature, there is a problem that its use is limited in electronic devices and automobiles, whose insides may become hot. Furthermore, the problem of color tone and the problem of further color tone deterioration when used in a high-temperature environment have not been solved.

[0005] For this reason, as resins for injection molding with improved orientation birefringence and heat resistance, a copolymer obtained by hydrogenating aromatic double bonds of a copolymer obtained by polymerizing a monomer composition containing a (meth)acrylic acid ester monomer and an aromatic vinyl monomer (Patent Document 3) and a (meth)acrylic resin having a glutarimide unit with a ring structure in the main chain (Patent Document 4) have been proposed. However, although the orientation birefringence of these resins is low, the photoelastic coefficient is not sufficiently reduced, so there is a drawback in that birefringence occurs due to residual strain during molding and stress generated when fixing optical components to equipment.

[0006] For this reason, resin materials that reduce both orientation birefringence and photoelasticity in injection molded pieces and have high heat resistance have been proposed, such as a non-birefringent resin material (Patent Document 5) made of a composition containing a resin such as glutarimide acrylic resin and a graft copolymer, and a methacrylic copolymer (Patent Document 6) having a ring structure in the main chain obtained from a monomer containing a methacrylate monomer and two or more types of N-substituted maleimide monomers. However, a composition containing multiple resins that are not completely compatible as in Patent Document 5 has limited application as an optical component because the haze increases and transparency deteriorates as the molded body becomes thicker. Although the methacrylic resin in Patent Document 6 has low orientation birefringence and photoelastic coefficient even as an injection molded body, there are problems such as a decrease in color tone caused by N-substituted maleimide, and when used in complex molded bodies with variable thickness such as lenses and prisms, or thin molded bodies such as light guide plates, high-temperature molding is required to increase fluidity, which further causes a decrease in color tone. Therefore, a resin composition that has low orientation birefringence and low photoelasticity, excellent heat resistance, and higher transparency is desired as a substitute for glass.

[0007] In addition, among the color tone deterioration of the methacrylic resin containing a structural unit having a ring structure in the main chain, for example, it has been reported that the color tone deterioration caused by N-substituted maleimide is caused by fluorescent coloring components. For example, Patent Document 7 describes that N-substituted maleimide or impurities of N-substituted maleimide are denatured into fluorescent coloring substances by heating them to 300°C or higher or by subjecting them to a volatilizing device having shear, which causes color tone deterioration, but there is a problem that the technology for reducing the substances that cause coloring is still insufficient. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2006-308682 A [Patent Document 2] International Publication No. 2015 / 098980 [Patent Document 3] JP 2008-15199 A [Patent Document 4] JP 2006-328330 A [Patent Document 5] International Publication No. 2015 / 098775 [Patent Document 6] International Publication No. 2011 / 149088 [Patent Document 7] JP 2020-63436 A Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide pellets, a molded article, and a method for producing the molded article, which are made of a methacrylic resin composition containing a methacrylic resin containing a structural unit derived from an N-substituted maleimide monomer in its main chain, and which have improved color tone and fluorescence intensity. [Means for solving the problem]

[0010] Means for Solving the Problems of the Prior Art As a result of intensive investigations, the present inventors have found that the above-mentioned problems can be solved by reducing the amount of fluorescent coloring substances contained in pellets made of a methacrylic resin composition containing a methacrylic resin containing a structural unit derived from an N-substituted maleimide monomer in its main chain.

[0011] That is, the present invention is as follows. [1] A pellet made of a methacrylic resin composition containing a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide monomer in the main chain, the pellet containing less than 0.30 ppm by mass of 2-amino-N-substituted maleimide. [2] The pellet according to [1], wherein the pellet has a reflection color tone YI of 10 or less. [3] The pellet according to [1] or [2], wherein a 20 w / v % chloroform solution of the pellet has an average transmittance of 90% or more for light having a wavelength of 400 nm to 450 nm, as measured using a 10 cm optical path length cell. [4] The pellet according to any one of [1] to [3], wherein the fluorescence quantum yield when the fine powder of the pellet is excited with light having a wavelength of 400 nm and a half-value width of 5 nm is 0.010 or less. [5] The pellet according to any one of [1] to [4], wherein the content of 2-amino-N-substituted maleimide per structural unit (X) derived from an N-substituted maleimide monomer in the methacrylic resin in the pellet (amount of 2-amino-N-substituted maleimide / amount of structural unit (X) derived from an N-substituted maleimide monomer) is less than 1.5 ppm by mass. [6] The pellet according to any one of [1] to [5], wherein the methacrylic resin composition contains 50 mass% or more of a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide monomer in its main chain, based on 100 mass% of the methacrylic resin composition. [7] The pellet according to any one of [1] to [6], wherein the methacrylic resin contains 3% by mass or more of a structural unit (X) derived from an N-substituted maleimide monomer in the main chain, based on 100% by mass of the methacrylic resin. [8] A molded article obtained by molding the pellet according to any one of [1] to [7]. [9] A method for producing a molded article containing a methacrylic resin composition, comprising: A step of polymerizing a methacrylic acid ester monomer, an N-substituted maleimide monomer, and optionally other vinyl monomers copolymerizable with the methacrylic acid ester monomer to obtain a methacrylic resin, and then optionally adding additives to obtain a methacrylic resin composition; forming the methacrylic resin composition into pellets; The pellets are exposed to a wavelength of 360 to 460 nm and an integrated light intensity of 0.1 to 10,000 W·hr / cm 2 and a step of heating and melting the light-irradiated pellets to obtain a molten material; and a step of injection molding the molten material to obtain a molded body. The method for producing a molded body comprising the steps of: Effect of the Invention

[0012] According to the present invention, it is possible to obtain pellets, a molded product, and a method for producing a molded product, which are made of a methacrylic resin composition containing a methacrylic resin containing a structural unit derived from an N-substituted maleimide monomer in the main chain, and which have improved color tone and fluorescence intensity. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic diagram of a rectangular molded piece used in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Below, we will explain in detail the form for implementing the present invention (hereinafter referred to as the "present embodiment"). However, the present invention is not limited to the following description and can be implemented in various modifications within the scope of its gist.

[0015] (Methacrylic resin) The methacrylic resin of the present embodiment is a methacrylic resin that contains a structural unit derived from a methacrylic acid ester monomer and contains a structural unit (X) derived from an N-substituted maleimide monomer in the main chain, and optionally contains other vinyl monomer units (Y) that are copolymerizable with the methacrylic acid ester monomer.

[0016] Each monomer structural unit will be described below.

[0017] -Structural units derived from methacrylate ester monomers- First, the structural unit derived from a methacrylic acid ester monomer will be described. The structural unit derived from a methacrylic acid ester monomer is formed, for example, from a monomer selected from the methacrylic acid esters shown below. Examples of methacrylic acid esters include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, cyclooctyl methacrylate, tricyclodecyl methacrylate, dicyclooctyl methacrylate, tricyclododecyl methacrylate, isobornyl methacrylate, phenyl methacrylate, benzyl methacrylate, 1-phenylethyl methacrylate, 2-phenoxyethyl methacrylate, 3-phenylpropyl methacrylate, and 2,4,6-tribromophenyl methacrylate. These monomers may be used alone or in combination of two or more kinds. Among the above methacrylic acid esters, methyl methacrylate and benzyl methacrylate are preferred in that the resulting methacrylic resin has excellent transparency and weather resistance. The structural unit derived from the methacrylic acid ester monomer may be contained in only one type, or in two or more types.

[0018] The content of the structural unit derived from the methacrylic acid ester monomer is preferably 50 to 97% by mass, more preferably 55 to 97% by mass, even more preferably 55 to 95% by mass, still more preferably 60 to 93% by mass, and particularly preferably 60 to 90% by mass, based on 100% by mass of the methacrylic resin, from the viewpoint of imparting sufficient heat resistance to the methacrylic resin by the structural unit (X) derived from the N-substituted maleimide monomer contained in the main chain described later. The content of structural units derived from methacrylic acid ester monomers is 1 H-NMR measurement and 13 It can be determined by C-NMR measurement. 1 H-NMR measurement and 13 C-NMR measurement can be carried out, for example, using CDCl3 or DMSO-d6 as a measurement solvent at a measurement temperature of 40°C.

[0019] The structural unit (X) derived from the N-substituted maleimide monomer contained in the main chain will be described below.

[0020] -Structural unit (X) derived from N-substituted maleimide monomer- The structural unit (X) derived from the N-substituted maleimide monomer may be at least one selected from a monomer represented by the following formula (1) and / or a monomer represented by the following formula (2), and is preferably formed from both of the monomers represented by the following formula (1) and the following formula (2).

[0021] [ka] In formula (1), R 1 represents an arylalkyl group having 7 to 14 carbon atoms or an aryl group having 6 to 14 carbon atoms; R 2 and R 3 each independently represents a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 14 carbon atoms, or an amino group. Also, R 2 When is an aryl group, R 2 may contain a halogen as a substituent. Also, R 1 may be substituted with a substituent such as a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, or a benzyl group.

[0022] [ka] In formula (2), R 4 represents a hydrogen atom, a cycloalkyl group having 3 to 12 carbon atoms, or an alkyl group having 1 to 12 carbon atoms; R 5 and R 6 each independently represents a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 14 carbon atoms, or an amino group.

[0023] Specific examples are given below. Examples of the monomer represented by formula (1) include N-phenylmaleimide, N-benzylmaleimide, N-(2-chlorophenyl)maleimide, N-(4-chlorophenyl)maleimide, N-(4-bromophenyl)maleimide, N-(2-methylphenyl)maleimide, N-(2-ethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, N-(2-nitrophenyl)maleimide, N-(2,4,6-trimethylphenyl)maleimide, N-(4- benzylphenyl)maleimide, N-(2,4,6-tribromophenyl)maleimide, N-naphthylmaleimide, N-anthracenylmaleimide, 3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1,3-diphenyl-1H-pyrrole-2,5-dione, 1,3,4-triphenyl-1H-pyrrole-2,5-dione, 2-anilino-N-phenylmaleimide, and the like. Among these monomers, N-phenylmaleimide and N-benzylmaleimide are preferred because the resulting methacrylic resin has excellent heat resistance and optical properties such as birefringence, and N-phenylmaleimide is particularly preferred from the viewpoint of heat resistance. Details of the use of N-phenylmaleimide as a monomer will be described later. These monomers may be used alone or in combination of two or more kinds.

[0024] Examples of the monomer represented by formula (2) include N-methylmaleimide, N-ethylmaleimide, Nn-propylmaleimide, N-isopropylmaleimide, Nn-butylmaleimide, N-isobutylmaleimide, Ns-butylmaleimide, Nt-butylmaleimide, Nn-pentylmaleimide, Nn-hexylmaleimide, Nn-heptylmaleimide, Nn-octylmaleimide, N-laurylmaleimide, N-stearylmaleimide, and N-cyclopentyl Examples of the maleimide include maleimide, N-cyclohexylmaleimide, 1-cyclohexyl-3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-diphenyl-1H-pyrrole-2,5-dione, and 2-cyclohexylamino-N-cyclohexylmaleimide. Among these monomers, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, and N-cyclohexylmaleimide are preferred because they provide excellent weather resistance to the methacrylic resin, and N-cyclohexylmaleimide is particularly preferred because it has excellent low moisture absorption, which is a requirement for optical materials in recent years. These monomers can be used alone or in combination of two or more.

[0025] In the methacrylic resin of this embodiment, it is particularly preferable to use a monomer represented by formula (1) and a monomer represented by formula (2) in combination, in order to express highly controlled birefringence characteristics. The molar ratio (X1 / X2) of the content (X1) of the structural unit derived from the monomer represented by formula (1) to the content (X2) of the structural unit derived from the monomer represented by formula (2) is preferably more than 0 and 15 or less, more preferably more than 0 and 10 or less. When the molar ratio X1 / X2 is within this range, the molded article containing the methacrylic resin of this embodiment maintains its transparency, does not turn yellow, and does not lose its environmental resistance, and exhibits good heat resistance and good photoelastic properties.

[0026] The content of the structural unit (X) derived from the N-substituted maleimide monomer is not particularly limited as long as the resulting composition satisfies the glass transition temperature range of this embodiment, but is preferably in the range of 5 to 40 mass%, more preferably in the range of 5 to 35 mass%, based on 100 mass% of the methacrylic resin. Within this range, the molded article containing the methacrylic resin can obtain a more sufficient improvement in heat resistance, and can obtain more preferable improvements in weather resistance, low water absorption, and optical properties. In addition, keeping the content of the structural unit (X) derived from the N-substituted maleimide monomer to 40 mass% or less is effective in preventing a decrease in the physical properties of the molded article containing the methacrylic resin due to a decrease in the reactivity of the monomer component during the polymerization reaction and an increase in the amount of unreacted remaining monomer.

[0027] -Other vinyl monomer units copolymerizable with methacrylate ester monomers (Y)- Other vinyl monomer units (Y) (hereinafter, sometimes referred to as (Y) monomer units) copolymerizable with the methacrylic acid ester monomer that can constitute the methacrylic resin of this embodiment include aromatic vinyl monomer units (Y-1), acrylic acid ester monomer units (Y-2), vinyl cyanide monomer units (Y-3), and monomer units (Y-4) other than these. The other vinyl monomer units (Y) copolymerizable with the methacrylic acid ester monomer may be used alone or in combination of two or more kinds. The monomer unit (Y) can be appropriately selected depending on the properties required for the methacrylic resin. When properties such as thermal stability, fluidity, mechanical properties, and chemical resistance are particularly required, at least one selected from the group consisting of an aromatic vinyl monomer unit (Y-1), an acrylic acid ester monomer unit (Y-2), and a vinyl cyanide monomer unit (Y-3) is suitable.

[0028] [Aromatic vinyl monomer unit (Y-1)] The monomer constituting the aromatic vinyl monomer unit (Y-1) constituting the methacrylic resin of this embodiment is not particularly limited, but is preferably an aromatic vinyl monomer represented by the following general formula (3).

[0029] [ka] In the general formula (3), R 13 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted, for example, with a hydroxyl group. R 14 is any one selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group having 6 to 8 carbon atoms, and an aryloxy group having 6 to 8 carbon atoms; R 14 may all be the same group or different groups. 14 They may combine together to form a ring structure. n represents an integer of 0 to 5.

[0030] Specific examples of the monomer represented by the above general formula (3) include, but are not limited to, styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, 1-vinylnaphthalene, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenylbenzene (α-methylstyrene), isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, isopropenyloctylbenzene, α-hydroxymethylstyrene, and α-hydroxyethylstyrene. Of the above, styrene and isopropenylbenzene are preferred, and styrene is more preferred from the viewpoints of imparting fluidity and reducing unreacted monomers by improving the polymerization conversion rate. These may be appropriately selected depending on the properties required for the methacrylic resin of this embodiment.

[0031] When the aromatic vinyl monomer unit (Y-1) is used, the content thereof is preferably 23% by mass or less, more preferably 20% by mass or less, even more preferably 18% by mass or less, still more preferably 15% by mass or less, and still more preferably 10% by mass or less, when the total amount of the structural unit derived from the methacrylic acid ester monomer and the structural unit (X) is taken as 100% by mass, taking into consideration the balance between heat resistance, reduction in residual monomer species, and flowability.

[0032] When the aromatic vinyl monomer unit (Y-1) is used in combination with the above-mentioned maleimide structural unit (X), the ratio (mass ratio) of the content of the (Y-1) monomer unit to the content of the (X) structural unit (i.e., (Y-1) content / (X) content) is preferably 0.3 to 5, from the viewpoints of flowability during processing of a film and the effect of reducing silver streaks by reducing residual monomers. From the viewpoint of maintaining good color tone and heat resistance, the upper limit is preferably not more than 5, more preferably not more than 3, and even more preferably not more than 1. From the viewpoint of reducing residual monomers, the lower limit is preferably not less than 0.3, and more preferably not less than 0.4. The above-mentioned aromatic vinyl monomer (Y-1) may be used alone or in combination of two or more kinds.

[0033] [Acrylic acid ester monomer unit (Y-2)] The monomer constituting the acrylic acid ester monomer unit (Y-2) constituting the methacrylic resin of this embodiment is not particularly limited, but is preferably an acrylic acid ester monomer represented by the following general formula (4).

[0034] [ka] In the general formula (4), R 15 represents a hydrogen atom or an alkoxy group having 1 to 12 carbon atoms; R 16 represents an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms.

[0035] As a monomer for forming the acrylic acid ester monomer unit (Y-2), from the viewpoint of enhancing weather resistance, heat resistance, fluidity, and thermal stability in the methacrylic resin for the film of this embodiment, preferred are methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, phenyl acrylate, and the like, more preferred are methyl acrylate, ethyl acrylate, and n-butyl acrylate, and from the viewpoint of easy availability, methyl acrylate and ethyl acrylate are even more preferred. The acrylic acid ester monomer unit (Y-2) may be used alone or in combination of two or more kinds.

[0036] When the acrylic acid ester monomer unit (Y-2) is used, the content thereof is preferably 5% by mass or less, and more preferably 3% by mass or less, when the total amount of the structural unit derived from the methacrylic acid ester monomer and the structural unit (X) is taken as 100% by mass, from the viewpoints of heat resistance and thermal stability.

[0037] [Cyanide vinyl monomer unit (Y-3)] The monomer constituting the vinyl cyanide monomer unit (Y-3) constituting the methacrylic resin of this embodiment is not particularly limited, but examples thereof include acrylonitrile, methacrylonitrile, ethacrylonitrile, vinylidene cyanide, etc., and among these, acrylonitrile is preferred from the viewpoints of ease of availability and chemical resistance. The vinyl cyanide monomer unit (Y-3) may be used alone or in combination of two or more kinds.

[0038] When the vinyl cyanide monomer unit (Y-3) is used, the content thereof is preferably 15% by mass or less, more preferably 12% by mass or less, and even more preferably 10% by mass or less, when the total amount of the structural unit derived from the methacrylic acid ester monomer and the structural unit (X) is taken as 100% by mass, from the viewpoint of maintaining solvent resistance and heat resistance.

[0039] [Monomer unit (Y-4) other than (Y-1) to (Y-3)] The monomer constituting the monomer unit (Y-4) other than (Y-1) to (Y-3) constituting the methacrylic resin of this embodiment is not particularly limited, and examples thereof include amides such as acrylamide and methacrylamide; glycidyl compounds such as glycidyl (meth)acrylate and allyl glycidyl ether; unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, and fumaric acid, and semi-esterified products or anhydrides thereof; unsaturated alcohols such as methallyl alcohol and allyl alcohol; olefins such as ethylene, propylene, and 4-methyl-1-pentene; and vinyl compounds or vinylidene compounds other than those mentioned above, such as vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinyl pyrrolidone, and N-vinyl carbazole. Further, examples of crosslinkable compounds having a plurality of reactive double bonds include compounds in which both terminal hydroxyl groups of ethylene glycol or its oligomers are esterified with acrylic acid or methacrylic acid, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate; compounds in which hydroxyl groups of two alcohols are esterified with acrylic acid or methacrylic acid, such as neopentyl glycol di(meth)acrylate and di(meth)acrylate; compounds in which polyhydric alcohol derivatives, such as trimethylolpropane and pentaerythritol, are esterified with acrylic acid or methacrylic acid; and polyfunctional monomers, such as divinylbenzene.

[0040] Among the monomers constituting the above-mentioned (Y) monomer unit, at least one selected from the group consisting of methyl acrylate, ethyl acrylate, styrene, and acrylonitrile is preferred from the viewpoint of availability.

[0041] The content of the other vinyl monomer unit (Y) copolymerizable with the methacrylic acid ester monomer is 0 to 20 mass%, preferably 0 to 18 mass%, and more preferably 0 to 15 mass%, based on 100 mass% of the methacrylic resin, from the viewpoint of enhancing the effect of imparting heat resistance by the (X) structural unit. In particular, when a crosslinkable polyfunctional (meth)acrylate having a plurality of reactive double bonds is used as the (Y) monomer unit, the content of the (Y) monomer unit is preferably 0.5 mass % or less, more preferably 0.3 mass % or less, and even more preferably 0.2 mass % or less, from the viewpoint of the fluidity of the polymer.

[0042] In particular, in this embodiment, from the viewpoint of the heat resistance and optical properties of a molded article containing a methacrylic resin, when the total amount of the (X) structural unit and the (Y) monomer unit is taken as 100 mass%, the content of the (X) structural unit is 45 to 100 mass%, and the content of the (Y) structural unit is 0 to 55 mass%, and the content of the (X) structural unit is preferably 50 to 100 mass%, more preferably 50 to 90 mass%, and even more preferably 50 to 80 mass%.

[0043] Hereinafter, the case where the structural unit (X) derived from the N-substituted maleimide monomer contained in the main chain contains a structural unit derived from N-phenylmaleimide will be described. When the structural unit (X) derived from the N-substituted maleimide monomer contained in the main chain contains a structural unit derived from N-phenylmaleimide, N-phenylmaleimide is used as the raw material.

[0044] The content of the structural unit derived from N-phenylmaleimide is not particularly limited as long as the obtained composition satisfies the glass transition temperature range of this embodiment, but is preferably in the range of 5 to 40 mass %, more preferably in the range of 5 to 35 mass %, based on 100 mass % of the methacrylic resin. Within this range, the molded article containing the methacrylic resin can obtain a more sufficient improvement in heat resistance, and can obtain more preferable improvements in weather resistance, low water absorption, and optical properties. In addition, keeping the content of structural units derived from the N-phenylmaleimide monomer to 40 mass% or less is effective in preventing a decrease in the physical properties of the molded article containing the methacrylic resin due to a decrease in the reactivity of the monomer component during the polymerization reaction and an increase in the amount of unreacted remaining monomer.

[0045] (N-phenylmaleimide) N-substituted maleimide compounds, typified by N-phenylmaleimide (phMI), can be produced by, but not limited to, (a) a method of dehydrating maleic anhydride and primary amines in one step; (b) a method of generating maleamic acids from maleic anhydride and primary amines and subjecting the maleamic acids to a dehydrating, ring-closing imidization reaction; (c) a method of subjecting corresponding maleamic acid monoesters to a ring-closing imidization reaction. Of these, method (b) is preferred, that is, for example, as a method for producing N-phenylmaleimide, a method of reacting maleic anhydride with aniline as raw materials to generate N-phenylmaleamic acid (PMA) and subjecting the N-phenylmaleamic acid to a dehydrating, ring-closing imidization reaction is particularly preferred.

[0046] In producing N-phenylmaleimide by the above method (b), aniline and maleic acid are produced by hydrolysis of the intermediate N-phenylmaleamic acid (PMA). This produced aniline, or aniline derived from the raw material, reacts with the target product N-phenylmaleimide to produce 2-anilino-N-phenylsuccinimide (APSI) (see the reaction formula below).

[0047] [ka]

[0048] Here, N-phenylmaleimide (phMI) as used in the present invention is a compound having a chemical structure represented by the following formula.

[0049] [ka]

[0050] Furthermore, N-phenylmaleamic acid (PMA) as used in the present invention is a compound having the chemical structure represented by the following formula.

[0051] [ka]

[0052] In addition, 2-anilino-N-phenylsuccinimide (APSI) as used in the present invention is a compound having a chemical structure represented by the following formula.

[0053] [ka]

[0054] As described above, the intermediate PMA undergoes either a dehydration ring-closing imidization reaction to give the target product phMI, or a hydrolysis reaction to produce aniline and maleic acid, which then reacts with phMI to produce APSI as a by-product. However, the entire amount of PMA does not necessarily undergo either reaction and is present as an impurity in phMI.

[0055] Thus, N-phenylmaleimide (phMI) contains PMA and APSI as impurities. If phMI containing these impurities is used as one component of a copolymerization monomer, PMA and APSI are later converted to phMI and its analogues via dehydration condensation reactions, oxidation reactions, etc., and there is a risk that the quality of the molded product, such as the appearance, heat resistance, and strength, may deteriorate, so it is desirable to reduce the content of these impurities as much as possible.

[0056] As a result of the research by the present inventors, it was confirmed by the ultraviolet-visible light absorption spectrum that the average gram absorption coefficient at 400-500 nm increases from 1.6 L / (g·cm) to 35.5 L / (g·cm) for PMA and from 0.02 L / (g·cm) to 3.3 L / (g·cm) for APSI by heating each of the simple substances at 200°C for 10 minutes, and it was revealed that PMA and APSI are decomposed or denatured into components having color in the visible light region by heating. In addition, as a result of detailed analysis, it was revealed that one of the components having color caused by heating is 2-anilino-N-phenylmaleimide (anilino-phMI). That is, it was found in the present invention that the content of the above-mentioned impurities PMA and APSI affects the quality, especially the coloring, of the copolymer obtained by using N-phenylmaleimide.

[0057] In the present invention, 2-anilino-N-phenylmaleimide (anilino phMI) is a compound having the chemical structure shown in the following formula.

[0058] [ka]

[0059] From the above results, when N-phenylmaleimide is used, it is preferable that PMA is 0.1 mass% or less and APSI is 0.01 mass% or less with respect to the total amount of N-phenylmaleimide. That is, when N-phenylmaleimide is used as a monomer, it is preferable to use N-phenylmaleimide (phMI) containing 0.1 mass% or less of PMA and 0.01 mass% or less of APSI as at least one component of the copolymerization monomer.

[0060] The content of PMA in N-phenylmaleimide is preferably 0.1% by mass or less based on the total amount of N-phenylmaleimide. Here, if N-phenylmaleimide with a PMA content exceeding 0.1% by mass is used as one component of the copolymerization monomer, the yellowness index YI of the molded product containing the copolymer produced tends to increase, which is undesirable. Although the detailed mechanism is not clear, it is presumed that the yellowness index YI increases because PMA is heated during polymerization and molding, and is converted to phMI by a dehydration condensation reaction, or the aniline produced by hydrolysis of a portion of PMA reacts with phMI to produce APSI, which is then oxidized during polymerization or molding to convert to a phMI analogue, such as anilino phMI. The content of PMA in N-phenylmaleimide is preferably 0.1% by mass or less, more preferably 0.06% by mass or less, further preferably 0.05% by mass or less, and particularly preferably 0.02% by mass or less, based on the total amount of N-phenylmaleimide. The lower limit of the content of PMA in N-phenylmaleimide is preferably as low as possible (i.e., 0% by mass), but from an industrial viewpoint, it is usually more than 0% by mass and preferably 0.01% by mass or more. In this specification, the PMA content is a value that can be measured by the method described in the Examples below.

[0061] In addition, the content of APSI in N-phenylmaleimide is preferably 0.01% by mass or less based on the total amount of N-phenylmaleimide. Here, if N-phenylmaleimide with the content of APSI exceeding 0.01% by mass is used as one component of the copolymerization monomer, the yellowness index YI of the molded article containing the copolymer produced tends to increase, which is not preferable. Although the detailed mechanism is not clear, it is presumed that the coloring occurs not only due to the coloring of APSI itself, but also due to the APSI being oxidized during polymerization or molding and converted into a phMI analogue, for example, anilino phMI. The content of APSI in N-phenylmaleimide is more preferably 0.008% by mass or less, and even more preferably 0.004% by mass or less, based on the total amount of N-phenylmaleimide. The lower limit of the APSI content in N-phenylmaleimide is preferably as low as possible (i.e., 0% by mass), but from an industrial viewpoint, it is usually more than 0% by mass and preferably 0.002% by mass or more. In this specification, the APSI content is a value that can be measured by the method described in the Examples section below.

[0062] (Production method of N-phenylmaleimide) The method for producing N-substituted maleimide compounds represented by N-phenylmaleimide is not particularly limited, and known methods can be applied in the same manner or with appropriate modifications, and commercially available N-phenylmaleimide can also be used. N-phenylmaleimide having reduced contents of PMA and APSI as described above can be obtained by the purification method described below. The above production method can be applied not only to N-phenylmaleimide but also to N-substituted maleimide compounds in general.

[0063] The characteristics of the methacrylic resin of this embodiment will be described below.

[0064] (glass transition temperature) The glass transition temperature (Tg) of the methacrylic resin of this embodiment is preferably higher than 120° C. and 160° C. or lower. If the glass transition temperature of the methacrylic resin exceeds 120° C., it is possible to more easily obtain heat resistance sufficient for use in recent optical components such as lens molded bodies, automobile components such as in-vehicle displays, film molded bodies for liquid crystal displays, optical films, etc. From the viewpoint of dimensional stability under the temperature of the usage environment, the glass transition temperature (Tg) is more preferably 125° C. or higher, and even more preferably 130° C. or higher. On the other hand, when the glass transition temperature (Tg) of the methacrylic resin is 160° C. or lower, melt processing at extremely high temperatures can be avoided, thermal decomposition of the resin, etc. can be suppressed, and a good product can be obtained. For the above-mentioned reasons, the glass transition temperature (Tg) is preferably 150° C. or lower. The glass transition temperature (Tg) can be determined by measurement in accordance with JIS-K7121. Specifically, it can be measured by the method described in the examples below.

[0065] (Weight average molecular weight) The methacrylic resin of the present embodiment has a weight average molecular weight (Mw) in terms of polymethyl methacrylate measured by gel permeation chromatography (GPC) in the range of preferably 65,000 to 220,000, more preferably 80,000 to 180,000, and even more preferably 90,000 to 150,000. When the weight average molecular weight (Mw) is within the above range, the balance between mechanical strength and flowability is excellent. Regarding the ratios among the Z-average molecular weight (Mz), weight-average molecular weight (Mw), and number-average molecular weight (Mn) as parameters representing molecular weight distribution, in the methacrylic resin of the present embodiment, taking into consideration the balance between fluidity and mechanical strength, Mw / Mn is preferably 1.5 to 3.0, more preferably 1.6 to 2.5, and even more preferably 1.6 to 2.3; Mz / Mw is preferably 1.3 to 2.0, more preferably 1.3 to 1.8, and even more preferably 1.4 to 1.7. The weight average molecular weight and number average molecular weight of the methacrylic resin can be measured by the method described in the Examples below.

[0066] (Methacrylic resin manufacturing method) The method for producing the methacrylic resin of this embodiment will be described below. In the production method of this embodiment, a batch system, a semi-batch system, or a continuous system can be used as the polymerization system. Here, the batch system is a process in which the reaction is started and proceeded after the entire amount of raw materials is charged into a reactor, and the product is recovered after the reaction is completed. The semi-batch system is a process in which either the raw materials are charged or the product is recovered simultaneously during the reaction, and the continuous system is a process in which both the raw materials are charged and the product is recovered simultaneously during the reaction. In this embodiment, the method for producing a methacrylic resin having a structural unit (X) derived from an N-substituted maleimide in the main chain is preferably a semi-batch system in which a part of the raw materials is charged after the reaction is started, from the viewpoint of precisely controlling the copolymer composition. In the method for producing the methacrylic resin in this embodiment, it is preferable to use polymerization of monomers by radical polymerization.

[0067] A method for producing a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide will be described in detail below. In this embodiment, a solution polymerization method is preferred as a method for producing a methacrylic resin having a structural unit (X) derived from an N-substituted maleimide monomer in the main chain.

[0068] The polymerization solvent to be used is not particularly limited as long as it can increase the solubility of the maleimide copolymer obtained by polymerization and can appropriately maintain the viscosity of the reaction solution for the purpose of preventing gelation, etc. Specific examples of the polymerization solvent that can be used include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and isopropylbenzene; ketones such as methyl isobutyl ketone, butyl cellosolve, methyl ethyl ketone, and cyclohexanone; and polar solvents such as dimethylformamide and 2-methylpyrrolidone. Furthermore, alcohols such as methanol, ethanol, and isopropanol may be used in combination as a polymerization solvent within a range that does not inhibit dissolution of the polymerization product during polymerization. These may be used alone or in combination of two or more.

[0069] The amount of the solvent during polymerization is not particularly limited as long as the polymerization proceeds, the precipitation of the copolymer or the monomers used does not occur during production, and the amount can be easily removed, but for example, when the total amount of the monomers to be blended is 100 parts by mass, the amount is preferably 10 to 200 parts by mass, more preferably 25 to 200 parts by mass, even more preferably 50 to 200 parts by mass, and even more preferably 50 to 150 parts by mass.

[0070] The polymerization temperature is not particularly limited as long as it is a temperature at which the polymerization proceeds, but is preferably 70 to 180° C., more preferably 80 to 160° C., even more preferably 90 to 150° C., and even more preferably 100 to 150° C. From the viewpoint of productivity, it is preferable to set the temperature at 70° C. or higher, and it is preferable to set the temperature at 180° C. or lower in order to suppress side reactions during polymerization and obtain a polymer with the desired molecular weight and quality.

[0071] The polymerization time is not particularly limited as long as it is a time that can obtain a required degree of polymerization at a required conversion rate, but from the viewpoint of productivity, etc., it is preferably 2 to 15 hours, more preferably 3 to 12 hours, and even more preferably 4 to 10 hours.

[0072] In the present embodiment, the polymerization conversion rate at the end of polymerization of the methacrylic resin having a structural unit (X) derived from an N-substituted maleimide monomer in the main chain is preferably 93 to 99.9%, more preferably 95 to 99.9%, and even more preferably 97 to 99.8%. Here, the polymerization conversion rate is the ratio of the total mass of the monomers added to the polymerization system minus the total mass of the monomers remaining at the end of the polymerization to the total mass of the monomers added to the polymerization system.

[0073] Furthermore, the amount of N-substituted maleimide monomer remaining in the solution after polymerization (residual N-substituted maleimide amount) is preferably from 50 to 5000 ppm by mass, more preferably from 100 to 3000 ppm by mass, and further preferably from 200 to 1000 ppm by mass. The higher the polymerization conversion rate and the smaller the remaining amount of N-substituted maleimide, the less monomer will be circulated to the solvent recovery system, reducing the load on the purification system and increasing the unit consumption, which is economical. However, if the polymerization conversion rate is made too high or the remaining amount of N-substituted maleimide is reduced too much, the amount of colorable low-molecular-weight components will increase, which may have an adverse effect on the color tone and moldability.

[0074] During the polymerization reaction, a chain transfer agent may be added as necessary. The chain transfer agent may be any chain transfer agent used in general radical polymerization, and examples thereof include mercaptan compounds such as n-butyl mercaptan, n-octyl mercaptan, n-decyl mercaptan, n-dodecyl mercaptan, and 2-ethylhexyl thioglycolate; halogen compounds such as carbon tetrachloride, methylene chloride, and bromoform; and unsaturated hydrocarbon compounds such as α-methylstyrene dimer, α-terpinene, dipentene, and terpinolene. These may be used alone or in combination of two or more. These chain transfer agents may be added at any stage as long as the polymerization reaction is in progress, and there are no particular limitations on the addition stage. The amount of the chain transfer agent added may be 0.01 to 1 part by mass, and preferably 0.05 to 0.5 part by mass, based on 100 parts by mass of the total amount of monomers used in the polymerization.

[0075] During the polymerization reaction, a polymerization initiator may be added. As the polymerization initiator, any initiator generally used in radical polymerization can be used. Examples of the polymerization initiator include organic peroxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, di-t-butyl peroxide, lauroyl peroxide, benzoyl peroxide, t-butylperoxyisopropyl carbonate, t-amylperoxy-2-ethylhexanoate, t-amylperoxyisononanoate, and 1,1-di-t-butylperoxycyclohexane; azo compounds such as 2,2'-azobis(isobutyronitrile), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and dimethyl-2,2'-azobisisobutyrate; and the like. These may be used alone or in combination of two or more. These polymerization initiators may be added at any stage as long as the polymerization reaction is in progress. The amount of the polymerization initiator added may be 0.01 to 1 part by mass, and preferably 0.05 to 0.5 part by mass, relative to 100 parts by mass of the total amount of the monomers used in the polymerization.

[0076] In solution polymerization, it is important to reduce the dissolved oxygen concentration in the polymerization solution as much as possible. For example, the dissolved oxygen concentration is preferably 10 ppm or less. The dissolved oxygen concentration can be measured, for example, using a dissolved oxygen meter DO meter B-505 (manufactured by Iijima Electronics Co., Ltd.) Methods for decreasing the dissolved oxygen concentration can be appropriately selected from a method of bubbling an inert gas into the polymerization solution, a method of repeatedly pressurizing a container containing the polymerization solution to about 0.2 MPa with an inert gas before polymerization and then releasing the pressure, a method of passing an inert gas through a container containing the polymerization solution, and the like.

[0077] In order to reduce the difference in the bound monomer composition in copolymers with different molecular weights, it is preferable to carry out polymerization while adding some monomer units additionally so that the monomer composition in the polymerization system during polymerization becomes as uniform as possible. For example, the type, amount and timing of the additionally added monomer are adjusted so that the difference in the consumption rate of each monomer at the time when about 70% of the total amount of monomers finally added to the system is consumed is preferably 10% or less, more preferably 5% or less, and even more preferably 3% or less. Furthermore, polymerization is carried out so that the difference in the final conversion rate between each monomer at the end of polymerization is 10% or less, more preferably 5% or less, and even more preferably 3% or less. The consumption rate of a certain monomer at a certain point in time means the proportion of that monomer consumed in the polymerization reaction to the total amount of that monomer added, and the total amount of that monomer added includes both the monomer that has already been added and the monomer that has not yet been added at a certain point in time.

[0078] The method for recovering the polymer from the polymerization liquid obtained by solution polymerization is not particularly limited, and examples thereof include a method in which the polymerization liquid is added to an excess of a poor solvent such as a hydrocarbon solvent or an alcohol solvent in which the polymerization product obtained by polymerization is not dissolved, and then the mixture is treated with a homogenizer (emulsion dispersion), and unreacted monomers are separated from the polymerization liquid by pretreatment such as liquid-liquid extraction or solid-liquid extraction; or a method in which the polymerization solvent and unreacted monomers are separated via a process called a devolatilization process, and the polymerization product is recovered. The devolatilization step here refers to a step of removing volatile matters such as the polymerization solvent, residual monomers, and reaction by-products under heating and reduced pressure conditions.

[0079] Examples of equipment used in the devolatilization step include a devolatilizer consisting of a tubular heat exchanger and a devolatilization tank; thin-film evaporators such as Wiblen and Exeva manufactured by Kobelco Environmental Solutions Co., Ltd., and Contra and tilted blade Contra manufactured by Hitachi, Ltd.; and a vented extruder having a residence time and surface area sufficient to exhibit devolatilization performance. A devolatilization step using a devolatilization apparatus that combines two or more of these devices can also be used.

[0080] The treatment temperature in the devolatilizer is preferably 150 to 350° C., more preferably 170 to 300° C., and further preferably 200 to 280° C. By setting the temperature to be equal to or higher than the lower limit, the amount of remaining volatile matter can be suppressed, and by setting the temperature to be equal to or lower than the upper limit, coloration and decomposition of the obtained acrylic resin can be suppressed.

[0081] The degree of vacuum in the volatilizer is preferably in the range of 10 to 500 Torr, and more preferably in the range of 10 to 300 Torr. By setting the degree of vacuum to the upper limit or less, the amount of remaining volatile matter can be suppressed. Also, a degree of vacuum equal to or greater than the lower limit is practical for industrial implementation. The treatment time is appropriately selected depending on the amount of remaining volatile matter, but in order to suppress coloration and decomposition of the resulting acrylic resin, the shorter the treatment time, the better.

[0082] The polymer recovered through the devolatilization step may be processed into pellets in a step called a granulation step. In the granulation step, the molten resin may be extruded in the form of strands through a multi-hole die and processed into pellets by a cold cut method, an air hot cut method, or an underwater cut method.

[0083] When a vented extruder is used as the devolatilization device, the devolatilization step may serve as both the granulation step and the devolatilization step.

[0084] (Methacrylic resin composition) The methacrylic resin composition of the present embodiment contains the methacrylic resin of the present embodiment described above, and the content of 2-amino-N-substituted maleimide in the methacrylic resin composition is less than 0.30 mass ppm. The methacrylic resin composition may optionally contain additives in addition to the methacrylic resin of the present embodiment described above, and may also contain thermoplastic resins other than the methacrylic resin, rubber polymers, etc., or may contain only the methacrylic resin. The content of the above methacrylic resin in 100% by mass of the methacrylic resin composition is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and particularly preferably 80% by mass or more.

[0085] -2-amino-N-substituted maleimide- Although not all of the fluorescent coloring components contained in the methacrylic resin composition have been identified, the inventors' research has revealed that the composition contains 2-amino-N-substituted maleimide produced by the reaction of N-substituted maleimide with a primary amine. 2-amino-N-substituted maleimide is known to be a fluorescent coloring component in itself. As the 2-amino-N-substituted maleimide, for example, when N-phenylmaleimide and N-cyclohexylmaleimide are used as raw materials, 2-anilino-N-phenylmaleimide and 2-cyclohexylamino-N-cyclohexylmaleimide are mainly produced. In the methacrylic resin composition of this embodiment, the content of 2-amino-N-substituted maleimide in the methacrylic resin is reduced to less than 0.30 ppm by mass by the production method described below. The content of 2-amino-N-substituted maleimide is preferably 0 ppm by mass or more and less than 0.20 ppm by mass, more preferably 0 ppm by mass or more and less than 0.10 ppm by mass. Since the content of 2-amino-N-substituted maleimide in the methacrylic resin composition of this embodiment is within the above range, it has good color tone and fluorescent emission intensity.

[0086] In addition, the methacrylic resin composition of this embodiment is preferably one in which the content of 2-amino-N-substituted maleimide per structural unit (X) derived from an N-substituted maleimide monomer in the methacrylic resin (2-amino-N-substituted maleimide amount / N-substituted maleimide monomer derived structural unit (X) amount) is reduced to less than 1.5 mass ppm by a production method or the like described below. The content of 2-amino-N-substituted maleimide per structural unit (X) derived from an N-substituted maleimide monomer is more preferably 0 mass ppm or more and less than 1.0 mass ppm, and even more preferably 0 mass ppm or more and less than 0.8 mass ppm. Since the content of 2-amino-N-substituted maleimide per structural unit (X) derived from an N-substituted maleimide monomer is within the above range, the methacrylic resin composition of this embodiment has good color tone and fluorescent emission intensity. The content of 2-amino-N-substituted maleimide in the methacrylic resin composition and the content of 2-amino-N-substituted maleimide per structural unit (X) derived from the N-substituted maleimide monomer can be quantified by the method described in the Examples below. The content of 2-amino-N-substituted maleimide in the methacrylic resin composition of the present embodiment can be reduced by a means for reducing the content of 2-amino-N-substituted maleimide described below.

[0087] -Additives- The methacrylic resin composition according to the present embodiment may contain various additives within the range that does not significantly impair the effects of the present invention. The additives are not particularly limited, and examples thereof include antioxidants, light stabilizers such as hindered amine light stabilizers, ultraviolet absorbers, release agents, other thermoplastic resins, softeners / plasticizers such as paraffinic process oil, naphthenic process oil, aromatic process oil, paraffin, organic polysiloxane, and mineral oil, flame retardants, antistatic agents, inorganic fillers such as organic fibers and pigments such as iron oxide, reinforcing agents such as glass fibers, carbon fibers, and metal whiskers, colorants, organic phosphorus compounds such as phosphites, phosphonites, and phosphate esters, other additives, and mixtures thereof.

[0088] --Antioxidants-- The methacrylic resin composition according to the present embodiment preferably contains an antioxidant that suppresses deterioration and coloration during molding or use. The antioxidant is not limited to the following, but examples thereof include hindered phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. The methacrylic resin of the present embodiment is suitably used in various applications such as melt extrusion, injection molding, and film molding. The heat history during processing varies depending on the processing method, ranging from about several tens of seconds in an extruder to several tens of minutes to several hours in the molding processing of thick-walled products and sheet molding. When subjected to a long-term heat history, it is necessary to increase the amount of heat stabilizer added in order to obtain the desired heat stability. From the viewpoint of suppressing bleed-out of the heat stabilizer and preventing the film from sticking to the roll during film formation, it is preferable to use multiple types of heat stabilizers in combination, for example, it is preferable to use at least one selected from a phosphorus-based antioxidant and a sulfur-based antioxidant in combination with a hindered phenol-based antioxidant. These antioxidants may be used alone or in combination of two or more.

[0089] Examples of the hindered phenol-based antioxidant include, but are not limited to, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis(dodecylthiomethyl)-o-cresol, ethylene bis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[ 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-xylin)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2 ,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamine)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, and the like. In particular, pentaerythritol terakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, and 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate are preferred.

[0090] In addition, as the hindered phenol-based antioxidant as the antioxidant, a commercially available phenol-based antioxidant may be used. Examples of such commercially available phenol-based antioxidants include, but are not limited to, Irganox 1010 (Irganox 1010: pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], manufactured by BASF), Irganox 1076 (Irganox 1076: octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), Irganox 1330 (Irganox 1330: octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), and the like. 1330: 3,3',3'',5,5',5''-hexa-t-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, manufactured by BASF), Irganox 3114 (Irganox 3114: 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF), Irganox 3125 (Irganox 3125, manufactured by BASF), Adeka STAB AO-60 (pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], manufactured by ADEKA), Adeka STAB AO-80 (3,9-bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, manufactured by ADEKA), Sumilizer BHT (Sumilizer BHT, manufactured by Sumitomo Chemical), Cyanox 1790 (Cyanox 1790, manufactured by Cytec), Sumilizer GA-80 (Sumilizer GA-80, manufactured by Sumitomo Chemical), Sumilizer GS (Sumilizer Examples of such compounds include GS (2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, manufactured by Sumitomo Chemical), Sumilizer GM (2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, manufactured by Sumitomo Chemical), and Vitamin E (manufactured by Eisai). Among these commercially available phenolic antioxidants, Irganox 1010, Adeka STAB AO-60, Adeka STAB AO-80, Irganox 1076, Sumilizer GS, and the like are preferred from the viewpoint of the effect of imparting thermal stability to the resin. These may be used alone or in combination of two or more.

[0091] In addition, examples of the phosphorus-based antioxidant as the antioxidant include, but are not limited to, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl ester phosphorous acid, tetrakis(2,4-di-t-butylphenyl)(1,1-biphenyl)-4,4'-diyl bisphosphonite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-t-butyl-4-methyl phenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetrakis(2,4-t-butylphenyl)(1,1-biphenyl)-4,4'-diylbisphosphonite, di-t-butyl-m-cresyl-phosphonite, 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, and the like. Furthermore, commercially available phosphorus-based antioxidants may be used as the phosphorus-based antioxidant. Examples of commercially available phosphorus-based antioxidants include, but are not limited to, Irgafos 168 (Irgafos 168: tris(2,4-di-t-butylphenyl)phosphite, manufactured by BASF), Irgafos 12 (Irgafos 12: tris[2-[[2,4,8,10-tetra-t-butyldibenzo[d,f][1,3,2]dioxaphosphen-6-yl]oxy]ethyl]amine, manufactured by BASF), Irgafos 38 (Irgafos 38: bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl ester phosphorous acid, manufactured by BASF), ADK STAB 329K (ADK STAB-229K, manufactured by ADEKA), ADK STAB PEP-36 (ADK STAB PEP-36, manufactured by ADEKA), ADK STAB PEP-36A, ADK STAB PEP-8, ADK STAB HP-10, ADK STAB HP-10, ADK STAB 2112, manufactured by ADEKA, ADK STAB 1178, manufactured by ADEKA, ADK STAB 1500, manufactured by ADEKA, Sandstab P-EPQ, manufactured by Clariant, Weston 618, manufactured by GE, Weston 619G, manufactured by GE, Ultranox 626, manufactured by GE, Sumilizer GP GP: 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, manufactured by Sumitomo Chemical Co., Ltd.), HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, manufactured by Sanko Co., Ltd.), and the like. Among these commercially available phosphorus-based antioxidants, from the viewpoint of the effect of imparting thermal stability to the resin and the effect of using them in combination with various other antioxidants, Irgafos 168, ADK STAB PEP-36, ADK STAB PEP-36A, ADK STAB HP-10, and ADK STAB 1178 are preferred, with ADK STAB PEP-36A and ADK STAB PEP-36 being particularly preferred. These phosphorus-based antioxidants may be used alone or in combination of two or more kinds.

[0092] In addition, examples of the sulfur-based antioxidant as the antioxidant include, but are not limited to, 2,4-bis(dodecylthiomethyl)-6-methylphenol (Irganox 1726, manufactured by BASF), 2,4-bis(octylthiomethyl)-6-methylphenol (Irganox 1520L, manufactured by BASF), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1 ,3-diylbis[3-dodecylthio]propionate] (ADEKA STAB AO-412S, manufactured by ADEKA Corporation), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthio]propionate] (ChemiNox PLS, manufactured by Chemipro Chemical Co., Ltd.), and di(tridecyl) 3,3'-thiodipropionate (AO-503, manufactured by ADEKA Corporation). Among these commercially available sulfur antioxidants, ADK STAB AO-412S and Cheminox PLS are preferred from the viewpoints of the effect of imparting thermal stability to the resin, the effect of using them in combination with various antioxidants, and ease of handling. These sulfur-based antioxidants may be used alone or in combination of two or more kinds.

[0093] The content of the antioxidant may be any amount that provides the effect of improving thermal stability. If the content is excessive, problems such as bleeding out during processing may occur. Therefore, the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, even more preferably 0.8 parts by mass or less, still more preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin.

[0094] The timing of adding the antioxidant is not particularly limited, and examples thereof include a method of adding the antioxidant to a monomer solution before polymerization and then initiating polymerization, a method of adding the antioxidant to a polymer solution after polymerization and mixing it and then subjecting it to a devolatilization step, a method of adding the antioxidant to a molten polymer after devolatilization and then mixing it and then pelletizing it, a method of adding the antioxidant when the pellets after devolatilization and pelletization are melt-extruded again, etc. Among these, from the viewpoint of preventing thermal deterioration and coloration in the devolatilization step, it is preferable to add the antioxidant to a polymer solution after polymerization and mix it, add it before the devolatilization step, and then subject it to the devolatilization step.

[0095] --Hindered amine light stabilizer-- The methacrylic resin composition of the present embodiment may contain a hindered amine light stabilizer. The hindered amine light stabilizer is not particularly limited, but is preferably a compound containing three or more ring structures. Here, the ring structure is preferably at least one selected from the group consisting of an aromatic ring, an aliphatic ring, an aromatic heterocycle, and a non-aromatic heterocycle, and when one compound has two or more ring structures, they may be the same or different from each other.

[0096] Examples of the hindered amine light stabilizer include, but are not limited to, bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, N ,N'-Bis(2,2,6,6-tetramethyl-4-piperidyl)-N,N'-diformylhexamethylenediamine, polycondensation product of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{2,2,6,6-tetramethyl- 4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, 1,2,2,6,6-pentamethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5. reaction products of 2,2,6,6-tetramethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, reaction products of 2,2,6,6-tetramethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, bis(1-undecaneoxy-2,2,6,6-tetramethylpiperidin-4-yl)carbonate, 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, and 2,2,6,6-tetramethyl-4-piperidyl methacrylate. Among these, bis(1,2,2,6,6-pentamethyl-4-piperidyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate, a polycondensate of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine, and poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl} Preferred are {2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], a reaction product of 1,2,2,6,6-pentamethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, and a reaction product of 2,2,6,6-tetramethyl-4-piperidiol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol.

[0097] The content of the hindered amine light stabilizer may be any amount that provides the effect of improving light stability. If the content is excessive, problems such as bleeding out during processing may occur. Therefore, the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, even more preferably 0.8 parts by mass or less, still more preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin.

[0098] --Ultraviolet absorber-- The methacrylic resin composition of the present embodiment may contain an ultraviolet absorber. The ultraviolet absorbent is not particularly limited, but is preferably an ultraviolet absorbent having a maximum absorption wavelength of 280 to 380 nm, and examples thereof include benzotriazole-based compounds, benzotriazine-based compounds, benzophenone-based compounds, oxybenzophenone-based compounds, benzoate-based compounds, phenol-based compounds, oxazole-based compounds, cyanoacrylate-based compounds, and benzoxazinone-based compounds.

[0099] Benzotriazole compounds include 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-benzotriazol-2-yl-4,6-di-tert-butylphenol, 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-t-butylphenol, 2-(2H-benzotriazol-2-yl)-4,6-di-t-butylphenol, 2-(2H-benzotriazol-2-yl)-4-(1,1 ,3,3-tetramethylbutyl)phenol, 2-(2H-benzotriazol-2-yl)-4-methyl-6-(3,4,5,6-tetrahydrophthalimidylmethyl)phenol, methyl 3-(3-(2H-benzotriazol-2-yl)-5-t-butyl-4-hydroxyphenyl)propionate / polyethylene glycol 300 reaction product, 2-(2H-benzotriazol-2-yl)-6-(linear and side chain dodecyl)-4-methylphenol, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-C7-9 side chain and linear alkyl esters. Among these, benzotriazole-based compounds having a molecular weight of 400 or more are preferred, and examples of commercially available products include Kemisorb (registered trademark) 2792 (manufactured by Chemipro Chemicals), Adeka STAB (registered trademark) LA31 (manufactured by ADEKA Corporation), and Tinuvin (registered trademark) 234 (manufactured by BASF).

[0100] Benzotriazine compounds include 2-mono(hydroxyphenyl)-1,3,5-triazine compounds, 2,4-bis(hydroxyphenyl)-1,3,5-triazine compounds, and 2,4,6-tris(hydroxyphenyl)-1,3,5-triazine compounds. Specific examples of the benzotriazine compounds include 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, and 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl). )-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4 -diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyethoxy)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3-5-triazine, 2,4,6-tris(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy -4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4- propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,Examples of the tris(2-hydroxy-3-methyl-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine include 6-tris(2-hydroxy-3-methyl-4-methoxycarbonylethyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, and 2,4,6-tris(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropan-2-yloxy)phenyl)-1,3,5-triazine. As the benzotriazine compound, commercially available products may be used, such as Kemisorb 102 (manufactured by Chemipro Chemicals), LA-F70 (manufactured by ADEKA Corporation), LA-46 (manufactured by ADEKA Corporation), TINUVIN 405 (manufactured by BASF), TINUVIN 460 (manufactured by BASF), TINUVIN 479 (manufactured by BASF), and TINUVIN 1577FF (manufactured by BASF). Among these, ultraviolet absorbers having a 2,4-bis(2,4-dimethylphenyl)-6-[2-hydroxy-4-(3-alkyloxy-2-hydroxypropyloxy)-5-α-cumylphenyl]-s-triazine skeleton (where "alkyloxy" refers to a long-chain alkyloxy group such as octyloxy, nonyloxy, decyloxy, etc.) are more preferably used because of their high compatibility with acrylic resins and excellent ultraviolet absorption properties.

[0101] As the ultraviolet absorber, from the viewpoints of compatibility with the resin and volatility upon heating, in particular, benzotriazole-based compounds and benzotriazine-based compounds having a molecular weight of 400 or more are preferred, and from the viewpoint of suppressing decomposition of the ultraviolet absorber itself due to heating during extrusion processing, benzotriazine-based compounds are particularly preferred.

[0102] The melting point (Tm) of the ultraviolet absorber is preferably 80° C. or higher, more preferably 100° C. or higher, even more preferably 130° C. or higher, and even more preferably 160° C. or higher. The ultraviolet absorber preferably has a weight loss rate of 50% or less, more preferably 30% or less, even more preferably 15% or less, even more preferably 10% or less, and even more preferably 5% or less, when heated from 23°C to 260°C at a rate of 20°C / min.

[0103] These ultraviolet absorbents may be used alone or in combination of two or more. By using two types of ultraviolet absorbents with different structures in combination, it is possible to absorb ultraviolet rays over a wide wavelength range.

[0104] The content of the ultraviolet absorbing agent is not particularly limited as long as it does not impair heat resistance, moist heat resistance, thermal stability, and moldability and exerts the effects of the present invention, but is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass or less, more preferably 0.25 to 3 parts by mass, and even more preferably 0.3 to 3 parts by mass, relative to 100 parts by mass of the methacrylic resin. When it is within this range, the balance between ultraviolet absorbing performance, moldability, etc. is excellent.

[0105] --Release agent-- The methacrylic resin composition of the present embodiment may contain a release agent. Examples of the release agent include, but are not limited to, fatty acid esters, fatty acid amides, fatty acid metal salts, hydrocarbon-based lubricants, alcohol-based lubricants, polyalkylene glycols, carboxylates, and hydrocarbon paraffin-based mineral oils.

[0106] The fatty acid ester that can be used as the release agent is not particularly limited, and any of the conventionally known fatty acid esters can be used. Examples of fatty acid esters that can be used include ester compounds of fatty acids having 12 to 32 carbon atoms, such as lauric acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, arachic acid, and behenic acid, with monohydric aliphatic alcohols, such as palmityl alcohol, stearyl alcohol, and behenyl alcohol, and polyhydric aliphatic alcohols, such as glycerin, pentaerythritol, dipentaerythritol, and sorbitan; and complex ester compounds of fatty acids, polybasic organic acids, and monohydric aliphatic alcohols or polyhydric aliphatic alcohols. Examples of such fatty acid ester lubricants include cetyl palmitate, butyl stearate, stearyl stearate, stearyl citrate, glycerin monocaprylate, glycerin monocaprate, glycerin monolaurate, glycerin monopalmitate, glycerin dipalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, glycerin monooleate, glycerin dioleate, glycerin trioleate, glycerin monolinoleate, and the like. glycerin monobehenate, glycerin mono 12-hydroxystearate, glycerin di 12-hydroxystearate, glycerin tri 12-hydroxystearate, glycerin diacetomonostearate, glycerin citrate fatty acid ester, pentaerythritol adipic acid stearate, partially saponified montanic acid ester, pentaerythritol tetrastearate, dipentaerythritol hexastearate, and sorbitan tristearate. These fatty acid ester-based lubricants can be used alone or in combination of two or more. Examples of commercially available products include the Rikemal series, Poem series, Rikestar series, and Rikemaster series manufactured by Riken Vitamin Co., Ltd., and the Excel series, Leodor series, Exepar series, and Coconard series manufactured by Kao Corporation, and more specific examples include Rikemal S-100, Rikemal H-100, Poem V-100, Rikemal B-100, Rikemal HC-100, Rikemal S-200, Poem B-200, Rikestar EW-200, Rikestar EW-400, Excel S-95, and Leodor MS-50.

[0107] The fatty acid amide-based lubricant is not particularly limited, and any of the conventionally known lubricants can be used. Examples of fatty acid amide lubricants include saturated fatty acid amides such as lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, and hydroxystearic acid amide; unsaturated fatty acid amides such as oleic acid amide, erucic acid amide, and ricinoleic acid amide; substituted amides such as N-stearyl stearic acid amide, N-oleyl oleic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, and N-oleyl palmitic acid amide; methylol amides such as methylol stearic acid amide and methylol behenic acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, and ethylene bisstearic acid amide (ethylene saturated fatty acid bisamides such as ethylene bisstearylamide, ethylene bisisostearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene bishydroxystearic acid amide, N,N'-distearyl adipamide, and N,N'-distearyl sebacic acid amide; unsaturated fatty acid bisamides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipamide, and N,N'-dioleyl sebacic acid amide; and aromatic bisamides such as m-xylylene bisstearic acid amide and N,N'-distearyl isophthalic acid amide. These fatty acid amide-based release agents can be used alone or in combination of two or more. Examples of commercially available products include the Diamid series (manufactured by Nippon Kasei Co., Ltd.), the Amide series (manufactured by Nippon Kasei Co., Ltd.), the Nikka Amide series (manufactured by Nippon Kasei Co., Ltd.), the Methylol Amide series, the Bis Amide series, the Slipax series (manufactured by Nippon Kasei Co., Ltd.), the Kaowax series (manufactured by Kao Corporation), the Fatty Acid Amide series (manufactured by Kao Corporation), and ethylene bis stearic acid amides (manufactured by Dainichi Chemical Industry Co., Ltd.).

[0108] The fatty acid metal salt refers to a metal salt of a higher fatty acid, and examples thereof include lithium stearate, magnesium stearate, calcium stearate, calcium laurate, calcium ricinoleate, strontium stearate, barium stearate, barium laurate, barium ricinoleate, zinc stearate, zinc laurate, zinc ricinoleate, zinc 2-ethylhexoate, lead stearate, dibasic lead stearate, lead naphthenate, calcium 12-hydroxystearate, and lithium 12-hydroxystearate. Of these, calcium stearate, magnesium stearate, and zinc stearate are particularly preferred because the resulting transparent resin composition has excellent processability and extremely excellent transparency. Examples of commercially available products include the SZ series, SC series, SM series, and SA series manufactured by Sakai Chemical Industry Co., Ltd. When the fatty acid metal salt is used, its content is preferably 0.2% by mass or less relative to 100% by mass of the methacrylic resin composition, from the viewpoint of maintaining transparency. The above-mentioned release agents may be used alone or in combination of two or more kinds.

[0109] The release agent to be used is preferably one having a decomposition onset temperature of 200° C. or higher. Here, the decomposition onset temperature can be measured based on the 1% mass loss temperature by TGA. The content of the release agent may be an amount that can obtain the effect as a release agent, and if the content is excessive, problems such as bleed-out during processing and extrusion failure due to screw slippage may occur, so the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, even more preferably 0.8 parts by mass or less, even more preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin. When the release agent is added in the amount within the above range, the decrease in transparency due to the addition of the release agent is suppressed, and there is a tendency that release failure during injection molding and sticking to a metal roll during sheet molding are suppressed, so this is preferable.

[0110] --Other thermoplastic resins-- The methacrylic resin composition of the present embodiment may contain a thermoplastic resin other than the methacrylic resin for the purpose of adjusting the birefringence or improving flexibility without impairing the object of the present invention. Other thermoplastic resins include, for example, polyacrylates such as polybutyl acrylate; styrene-based polymers such as polystyrene, styrene-methyl methacrylate copolymer, styrene-butyl acrylate copolymer, styrene-acrylonitrile copolymer, and acrylonitrile-butadiene-styrene block copolymer; and further, for example, acrylic rubber particles having a 3-4 layer structure described in JP-A-59-202213, JP-A-63-27516, JP-A-51-129449, JP-A-52-56150, etc.; rubbery polymers disclosed in JP-B-60-17406 and JP-A-8-245854; methacrylic rubber-containing graft copolymer particles obtained by multistage polymerization described in WO 2014-002491; and the like. Among these, from the viewpoint of obtaining good optical properties and mechanical properties, rubber-containing graft copolymer particles having a graft portion on their surface layer made of a composition compatible with styrene-acrylonitrile copolymers and methacrylic resins containing a structural unit (X) derived from an N-substituted maleimide monomer in the main chain are preferred. The average particle size of the above-mentioned acrylic rubber particles, methacrylic rubber-containing graft copolymer particles, and rubber polymer is preferably 0.03 to 1 μm, and more preferably 0.05 to 0.5 μm, from the viewpoint of improving the impact strength and optical properties of the molded article obtained from the composition of this embodiment.

[0111] The content of the other thermoplastic resin is preferably 0 to 50 parts by mass, and more preferably 0 to 25 parts by mass, based on 100 parts by mass of the methacrylic resin.

[0112] The glass transition temperature (Tg), weight average molecular weight (Mw), and number average molecular weight (Mn) for the methacrylic resin composition may be the same as those described above for the methacrylic resin.

[0113] (pellet) The pellets of this embodiment are made of a methacrylic resin composition containing a methacrylic resin that contains a structural unit (X) derived from an N-substituted maleimide monomer in the main chain. The pellets of this embodiment may contain the methacrylic resin of this embodiment described above, or may be made of the methacrylic resin composition of this embodiment described above.

[0114] The content of 2-amino-N-substituted maleimide in the pellets of this embodiment is the same as the content of 2-amino-N-substituted maleimide in the above-mentioned methacrylic resin composition. That is, the content of 2-amino-N-substituted maleimide in the pellets is less than 0.30 mass ppm, preferably 0 mass ppm or more and less than 0.20 mass ppm, more preferably 0 mass ppm or more and less than 0.10 mass ppm. Since the content of 2-amino-N-substituted maleimide in the pellets of this embodiment is in the above range, the pellets have good color tone and fluorescent emission intensity.

[0115] The content of 2-amino-N-substituted maleimide per structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin in the pellet of this embodiment (2-amino-N-substituted maleimide amount / N-substituted maleimide monomer derived structural unit (X) amount) is the same as the content of 2-amino-N-substituted maleimide per structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin in the above-mentioned methacrylic resin composition. That is, the content of 2-amino-N-substituted maleimide per structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin in the pellet is preferably less than 1.5 mass ppm, more preferably 0 mass ppm or more and less than 1.0 mass ppm, and even more preferably 0 mass ppm or more and less than 0.80 mass ppm. The pellets of this embodiment have a good color tone and fluorescent emission intensity because the content of 2-amino-N-substituted maleimide per structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin is within the above range. The content of 2-amino-N-substituted maleimide in the pellets and the content of 2-amino-N-substituted maleimide per structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin in the pellets can be quantified by the method described in the Examples below. The content of 2-amino-N-substituted maleimide in the pellets of this embodiment can be reduced by a means for reducing the content of 2-amino-N-substituted maleimide described below.

[0116] (Method for producing pellets of methacrylic resin composition) The method for producing the methacrylic resin composition, i.e., the method for producing pellets of the methacrylic resin composition, includes, for example, a method including a kneading step using a kneader such as an extruder, a heating roll, a kneader, a roller mixer, or a Banbury mixer. Among them, kneading using an extruder is preferred in terms of productivity. The kneading temperature may be in accordance with the preferred processing temperature of the polymer constituting the methacrylic resin or the other resin to be mixed, and is generally in the range of 140 to 300°C, preferably 180 to 280°C. In addition, it is preferable to provide a vent port in the extruder for the purpose of reducing volatile content. In addition, the method for producing pellets of the methacrylic resin composition preferably includes a light irradiation step, which is one of the means for reducing the content of 2-amino-N-substituted maleimide described below, as a post-step.

[0117] The pellets of this embodiment preferably have a reflection color tone YI of 10 or less, more preferably 5 or less, and further preferably 3 or less. Furthermore, the pellets of this embodiment have a reflection color tone YI difference ΔYI (YI of a pellet having a 2-amino-N-substituted maleimide content of 0.30 ppm by mass or more - YI of the pellets of this embodiment) compared to pellets produced without taking any measure for reducing the content of 2-amino-N-substituted maleimide described below, i.e., pellets having a 2-amino-N-substituted maleimide content of 0.30 ppm by mass or more) of preferably 1 or more, more preferably 3 or more, and even more preferably 5 or more. The reflected color tone YI value of the pellets can be measured by the method described in the Examples below.

[0118] The pellets of this embodiment preferably have a solution YI of 6 or less, more preferably 5 or less, and further preferably 4 or less. The solution YI value of the pellets can be measured by the method described in the Examples below.

[0119] The pellets of this embodiment are excellent in transmittance. The transmittance of the pellets of this embodiment is preferably improved by 3% or more, more preferably improved by 6% or more, and even more preferably improved by 9% or more in at least one wavelength band of 1 nm width, compared to the transmittance of pellets produced without carrying out the means for reducing the content of 2-amino-N-substituted maleimide described below, i.e., pellets having a content of 2-amino-N-substituted maleimide of 0.30 mass ppm or more. The wavelength at which the transmittance is improved is preferably a low wavelength (for example, any wavelength from 400 to 460 nm or all wavelengths from 400 to 460 nm). The pellets of this embodiment can be dissolved in a solvent and the transmittance measured to quantitatively evaluate the color tone improvement effect due to the reduction in the content of 2-amino-N-substituted maleimide. The average transmittance at wavelengths of 400 nm to 450 nm measured for a 20 w / v % chloroform solution of the pellets using a 10 cm optical path length cell is preferably 90% or more, more preferably 93% or more, and even more preferably 95% or more. The transmittance of the pellet can be measured by the method described in the Examples below.

[0120] The fluorescent quantum yield of the fine powder of the pellets of this embodiment when excited with light having a wavelength of 400 nm and a half-width of 5 nm is preferably 0.010 or less, more preferably 0.007 or less, and even more preferably 0.005 or less. If the fluorescent quantum yield is within the above range, the fluorescent emission is more suppressed and the pellets tend to have a better color tone. Specifically, the fluorescence quantum yield of the pellet can be measured by the method described in the Examples below.

[0121] (Molded body) By molding the pellets of the present embodiment, a molded article having improved color tone and fluorescence intensity can be obtained, which contains a methacrylic resin composition including a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide monomer in the main chain. Furthermore, it was found that when the pellets of this embodiment obtained through the light irradiation process were molded to obtain a molded body, the mold releasability during molding was slightly improved. Although the detailed mechanism by which this mold releasability is improved has not been clarified, it is presumed that by irradiating the pellets with light, reactive bonds, particularly double bonds and polar functional groups, among the color-derived components in the resin, are converted into saturated bonds or low-polarity bonds through some kind of photochemical change, thereby weakening the interaction with the mold surface, and as a result, the mold releasability is improved. In addition, the molded body obtained has only improved color tone and fluorescence intensity, and does not have any adverse effect on physical properties other than color tone, such as mechanical properties and thermal properties.

[0122] (Method of Manufacturing Molded Product) The method for producing the molded article of the present embodiment includes molding the pellets of the present embodiment. For the molding, various molding methods such as extrusion molding, injection molding, compression molding, calendar molding, inflation molding, and blow molding can be used. Among them, it is preferable to apply injection molding and injection compression molding from the viewpoint of productivity. Typically, injection molding consists of (1) an injection process in which resin is melted and the molten resin is filled into the cavity of a temperature-controlled mold; (2) a pressure holding process in which pressure is applied inside the cavity until the gate is sealed, and an amount of resin is injected equivalent to the amount of molten resin filled in the injection process that comes into contact with the mold and cools and shrinks; (3) a cooling process in which the molded body is held until the resin cools after the pressure holding process is released; and (4) the mold is opened and the cooled molded body is removed.

[0123] In this case, the molding temperature is preferably in the range of Tg+100° C. to Tg+160° C., and more preferably in the range of Tg+110° C. to Tg+150° C., based on the glass transition temperature of the methacrylic resin composition. Here, the molding temperature refers to the controlled temperature of a band heater wrapped around the injection nozzle. The mold temperature is preferably in the range of Tg-70°C to Tg, and more preferably in the range of Tg-50°C to Tg-20°C, based on the glass transition temperature (Tg) of the methacrylic resin composition.

[0124] The injection speed can be appropriately selected depending on the thickness and dimensions of the injection molded article to be obtained, and can be appropriately selected, for example, from the range of 200 to 1000 mm / sec. The pressure for holding can be appropriately selected depending on the shape of the injection molded article to be obtained, and can be appropriately selected, for example, within the range of 30 to 120 MPa. In the case of a thin-walled molded article with a fast solidification speed, holding pressure may not be applied. The pressure for holding the pressure referred to here is the pressure maintained by a screw for further feeding the molten resin from the gate after the molten resin has been filled.

[0125] Injection compression molding is an injection molding method in which the mold is opened slightly before the start of injection molding, and molten resin is filled into the mold at high speed and low pressure. After that, the mold clamping pressure is increased at high speed and a compression and holding pressure process is added to uniformly hold the pressure over the entire surface of the resin. This makes it possible to mold molded articles with excellent surface and optical properties. When attempting to obtain a thinner injection molded article, for example one having a thickness of less than 1 mm and a diagonal dimension of more than 100 mm, it is particularly preferable to employ injection compression molding, since this method produces a molded article with excellent optical properties and color tone.

[0126] In addition, when the injection molded body obtained by using the pellets of the above methacrylic resin composition is used as a light guide plate, the surface of the molded body may be provided with fine irregularities. By providing such fine irregularities, it is preferable that a reflective layer is not required to be provided by printing or the like. The fine irregularities are not particularly limited, but include irregularities having clear structural units such as rectangular parallelepiped, cylindrical, elliptical cylinder, triangular prism, sphere, aspheric surface, etc., irregularities having a rough shape such as a matte finish or hairline shape but not clear structural units, or combinations thereof, and irregularities having clear structural units but varying in shape, particularly size. As the shape of the irregularities, the height or recess of the shape can be 0.1 to 500 μm, and the pitch distance between the irregularities can be 10 to 1000 μm.

[0127] Various molded articles using pellets of the methacrylic resin and its resin composition of this embodiment can further be subjected to surface functionalization treatments such as anti-reflection treatment, transparent conductive treatment, electromagnetic wave shielding treatment, and gas barrier treatment.

[0128] -Means for reducing the content of 2-amino-N-substituted maleimide (means for improving the color tone of pellets and molded articles of methacrylic resin composition)- The present inventors discovered that the pellets of the methacrylic resin composition of the present embodiment and the molded article using the pellets have improved color tone and fluorescence intensity by reducing 2-amino-N-substituted maleimide, which is one of the fluorescent coloring components contained in the methacrylic resin composition, and have arrived at the invention. 2-amino-N-substituted maleimide is considered to be generated by impurities contained in the N-substituted maleimide monomer, which is the raw material of the methacrylic resin, or by denaturation of unreacted N-substituted maleimide remaining after the polymerization step and / or the devolatilization step, by heat, etc. Therefore, as a means for reducing the content of 2-amino-N-substituted maleimide, for example, (1) a method of irradiating a pellet of a methacrylic resin composition with light to convert the 2-amino-N-substituted maleimide contained in the methacrylic resin composition into another compound, or (2) a method of purifying the raw material N-substituted maleimide to remove impurities, specifically, PMA and APSI, which are the sources of the 2-amino-N-substituted maleimide, can be used.

[0129] --Light irradiation of pellets-- The method for producing pellets of the methacrylic resin composition of the present embodiment preferably includes, as a post-step for reducing the 2-amino-N-substituted maleimide content, a light irradiation step of irradiating pellets made of a methacrylic resin composition containing a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide monomer in its main chain with light having a wavelength of 360 to 460 nm. The molded article having an improved color tone can be obtained by molding the pellets irradiated with light according to this embodiment using the above-mentioned molded article manufacturing method. In particular, the present inventors have discovered light irradiation conditions that improve the color tone and fluorescence intensity uniformly throughout the pellet, while at the same time not adversely affecting the mechanical and thermal properties of the molded article during subsequent molding processing.

[0130] Although the mechanism is not entirely clear, it is assumed that the coloring components absorb the irradiated light and change to non-coloring components, thereby improving the transmittance (spectral transmittance) of the pellet and improving the color tone and fluorescence intensity. In other words, it is speculated that by irradiating the pellet with light of a wavelength in the absorption range of the coloring components to cause a photoreaction, the coloring components containing fluorescent compounds change to non-coloring components, reducing the reflective color tone YI value of the pellet, absorbance in the visible light range, and fluorescence quantum yield, making it easy to obtain pellets with improved color tone and fluorescence intensity. Among the absorption regions, the absorbance is particularly high in the wavelength range of 360 to 460 nm, and the influence on the YI value is large, so it is considered that irradiation with light including a wavelength of 360 to 460 nm is highly effective in improving color tone. In fact, the present inventors' investigations have revealed that the content of 2-amino-N-substituted maleimide in the methacrylic resin composition is reduced by irradiating with light having a wavelength of 360 to 460 nm. In other words, it has been confirmed that the photoreaction in which the 2-amino-N-substituted maleimide, which is a coloring component, absorbs the irradiated light and changes into a non-coloring component proceeds.

[0131] Examples of pellets in which the reflected color tone YI value is reduced (for example, the YI value is reduced by 1 or more) and the transmittance is improved by irradiation with light include the above-mentioned pellets. Among them, as described above, by using the above-mentioned methacrylic acid ester as the structural unit derived from the above-mentioned methacrylic acid ester monomer, by making the content of the structural unit derived from the above-mentioned methacrylic acid ester monomer 50% by mass or more, by making the content of the above-mentioned structural unit (X) 3 to 40% by mass, by making the content of the methacrylic resin 50% by mass or more, etc., the reflected color tone YI value of the pellets is more likely to be reduced and the transmittance is more likely to be improved by irradiation with light including a wavelength of 360 to 460 nm.

[0132] The output of the light to be irradiated is 0.001 to 10 W / cm 2 It is preferable that the range is 0.001 W / cm 2At light output lower than 10 W / cm, the photoreaction does not proceed sufficiently and long irradiation times are required, so there is a risk that the color tone will not be improved sufficiently. 2 When the light output is higher than 0.005 to 5 W / cm, part of the absorbed light is inactivated as heat energy, but the photoreaction and heat reaction may cause deterioration of the resin itself or the generation of new coloring components, and the decrease in transmittance may compete with the improvement of color tone, resulting in a decrease in color tone. 2 More preferably, it is 0.01 to 3 W / cm 2 It is preferable that the light output of the irradiated light satisfies the above range for the entire pellet, and it is more preferable that the light output is uniform over the entire surface. The optical output can be measured by a photometer using a photodiode or a power meter. In addition, the radiant flux (W) can be measured to determine the irradiated area (cm 2 The specific light output can be estimated by placing a light actinometer or power meter at a location that corresponds to the surface of the pellet to be irradiated with light and measuring the light output. In the above light irradiation, the light output is preferably constant during irradiation, but may be varied. When the light output is varied, there is no problem as long as the light output of the irradiated light is adjusted to satisfy the above range. The light may be irradiated from multiple directions or from one direction, but it is preferable to arrange the light sources uniformly from the viewpoint of uniform irradiation.

[0133] The cumulative light intensity of the light to be irradiated is 0.1 to 10,000 W·hr / cm 2 It is preferable that the range is 0.1 W hr / cm 2 At an integrated light dose lower than 10,000 W·hr / cm, the photoreaction does not proceed sufficiently and the improvement in fluorescence intensity and color tone tends not to occur sufficiently. 2If the integrated light intensity is higher than 0.5~5000W·hr / cm, some of the absorbed light will be inactivated as heat energy, but the photoreaction and heat reaction may cause deterioration of the resin itself and the generation of new coloring components, and the decrease in transmittance may compete with the improvement of color tone, resulting in a decrease in color tone. The integrated light intensity is 0.5~5000W·hr / cm 2 More preferably, it is 1.0 to 1000 W hr / cm 2 It is. The integrated light quantity can be measured using an integrated light meter using a photodiode or a power meter. The integrated light quantity can also be calculated using the radiation density (energy density, W / cm 2 ) is the time (hr) integral value, so if the radiant flux (W) can be measured, the irradiated area (cm 2 ) the energy density can be calculated, and the cumulative amount of light can be calculated based on the exposure time.

[0134] Regarding the time for light irradiation, a short time is desirable from the viewpoint of productivity, but if the pellets are irradiated with light during storage, a long time is also acceptable. The light irradiation may be performed continuously or discontinuously, but from the viewpoint of efficiency, it is preferable to perform the light irradiation continuously. Even when the light is irradiated discontinuously, it is preferable that the light output satisfies the above range.

[0135] The light irradiated to the pellets includes light having a wavelength of 360 to 460 nm, and preferably includes mainly light having a wavelength of 360 to 460 nm. The light may be light of a single wavelength, or may include light of multiple wavelengths. For example, light having a single wavelength or multiple wavelengths within the range of 360 to 460 nm, and light including light of a single wavelength or multiple wavelengths outside the range of 360 to 460 nm, etc. may be mentioned. Although there is no problem if the irradiated light contains a small amount of light with a wavelength shorter than 360 nm, it is preferable to use only light with a wavelength of 360 to 460 nm as the light source, since long-term irradiation of short-wavelength light of less than 360 nm with high optical output causes decomposition and coloring of the molded body. In order to minimize decomposition and coloring, for example, a light source that irradiates light so as not to contain light with a wavelength of less than 360 nm can be selected, or a filter that cuts out wavelengths other than the target wavelength can be combined. The light to be irradiated may contain light with a wavelength longer than 460 nm. The longer the wavelength, the less effect there is on the color tone. However, irradiation with light in the infrared region in particular raises the temperature of the pellet resin itself, and if the temperature rise is too great, there is a possibility that color tone may deteriorate due to heat. Therefore, it is preferable that the light be only in the visible light region. The phrase "mainly containing light with a wavelength of 360 to 460 nm" means that the spectral output of light with a wavelength of 360 to 460 nm in the light irradiated to the pellets is 50% or more of the total irradiated light.

[0136] The temperature of the pellets during light irradiation is preferably in the range of 20° C. or higher and 20° C. lower than the glass transition temperature of the methacrylic resin composition constituting the pellets, for the purpose of promoting the photoreaction. By irradiating with light within the above temperature range, the photoreaction is promoted and a sufficient color tone improvement effect can be obtained in a shorter time. Although a certain degree of color improvement can be achieved even if the temperature when irradiating the pellets with light is lower than 20°C, sufficient color improvement may not be expected unless the light is irradiated for a longer period of time. On the other hand, if light irradiation is performed at a temperature higher than a temperature 20°C lower than the glass transition temperature, the pellets may be heated above the glass transition region, which can lead to problems such as the pellets being unable to maintain their shape or the pellets fusing together. For example, when irradiating with light including light in the infrared region, it can be used without problems if the temperature of the pellets is adjusted to be 20° C. lower than the glass transition temperature, taking into account the effect of heating. Although the color tone improving effect can be obtained using only light without heating, it is considered that the color tone improving effect can be obtained in a short period of time by irradiating with light while heating to a certain extent, which is preferable from the viewpoint of productivity, and the temperature can be appropriately selected within the range of 20° C. to 20° C. or more lower than the glass transition temperature of the methacrylic resin composition depending on the usage conditions. The temperature is more preferably 30° C. or higher and not higher than a temperature 25° C. lower than the glass transition temperature of the methacrylic resin composition, and further preferably 40° C. or higher and not higher than a temperature 30° C. lower than the glass transition temperature. The pellet temperature can be measured by the method described in the Examples below.

[0137] The light source used for light irradiation can be appropriately selected from natural light such as sunlight and artificial light sources. Examples of artificial light sources include incandescent lamps, fluorescent lamps, halogen lamps, mercury lamps, metal halide lamps, xenon lamps, LEDs, lasers, etc. Among these, LEDs are preferred from the viewpoint of irradiating only light with a wavelength of 360 to 460 nm, which is particularly effective in improving color tone, and light sources can be used in appropriate combinations taking into consideration reaction promotion by heating, etc. When the rise in pellet temperature due to light irradiation becomes a problem, an infrared cut filter or a cooling mechanism using air or water cooling can be provided to prevent the pellets from maintaining their shape and suppressing deterioration in color tone due to temperatures above the glass transition region.

[0138] --Purification of N-phenylmaleimide-- The method for purifying N-phenylmaleimide of the present embodiment can be achieved by a conventionally known purification method, but it is preferable to repeat the purification steps or use stricter purification conditions, since this allows the product to be obtained efficiently and stably for a long period of time.

[0139] A preferred embodiment of the purification method of N-phenylmaleimide is described below, but is not limited to the following form. That is, for example, a method of dissolving solid phMI in an organic solvent, washing with water at 30° C. or less to remove impurities, and then drying, a method of dissolving solid phMI in an organic solvent, washing with an acidic or basic aqueous solution, and drying the solution, a method of completely dissolving solid phMI in an organic solvent, filtering with a filter to remove impurities, and then drying the filtrate, etc. can be used. Among them, the method of completely dissolving solid phMI in an organic solvent, filtering with a filter to remove impurities, and then drying the filtrate is more preferable in terms of suppressing hydrolysis of phMI.

[0140] The method for purifying N-phenylmaleimide in this embodiment is preferably a purification method using a filter filtration step that utilizes the difference in solubility between impurities and N-phenylmaleimide in a solvent.

[0141] Here, the organic solvent that can be used when purifying pHMI is not particularly limited, but is preferably a solvent that is insoluble or immiscible in water and inert (not involved in the reaction), such as an aromatic compound. Examples of such solvents include benzene, toluene, petroleum fractions with a boiling point of 50 to 120°C, xylene, ethylbenzene, isopropylbenzene, cumene, mesitylene, tert-butylbenzene, methoxybenzene, pseudocumene, trimethylhexane, octane, tetrachloroethane, nonane, chlorobenzene, ethylcyclohexane, petroleum fractions with a boiling point of 120 to 170°C, m-dichlorobenzene, sec-butylbenzene, p-dichlorobenzene, decane, p-cymene, o-dichlorobenzene, butylbenzene, decahydronaphthalene, tetrahydronaphthalene, dodecane, naphthalene, cyclohexylbenzene, petroleum fractions with a boiling point of 170 to 250°C, etc. The above organic solvents may be used alone or in the form of a mixture of two or more kinds. Among the above organic solvents, toluene, o-xylene, m-xylene and p-xylene are more preferred because of their superiority in solubility of N-phenylmaleamic acid (PMA) and filtration efficiency.

[0142] The amount of the organic solvent used is not particularly limited, but one that allows smooth filtration and has a large difference between the solubility of phMI and the solubility of PMA and APSI is selected. Furthermore, in consideration of the separation of phMI from the solvent after purification, it may be more advantageous to use a solvent with a low boiling point and purify under pressure. Here, the concentration of phMI during filter filtration is not particularly limited as long as it is a concentration at which phMI can be dissolved. Specifically, it is preferable to add and dissolve 1 to 50 g of organic solvent per 1 g of phMI, more preferably 5 to 30 g, and even more preferably 10 to 20 g.

[0143] In addition, the weight ratio of PMA to phMI contained in the mixture of phMI and an organic solvent to be filtered is PMA / phMI=6×10 -5 Here, it is preferable that the weight ratio of PMA to phMI is PMA / phMI=6×10 or less. -5 If the weight ratio of PMA to phMI is greater than 4×10, the PMA content in phMI may not be reduced sufficiently because too much PMA dissolves in the organic solvent and cannot be removed by filtration. -5 More preferably, PMA / phMI is 3×10 or less. -5 It is particularly preferable that the weight ratio is equal to or less than 1. The above weight ratio can be controlled by the temperature of the mixture and the type of solvent. PMA / phMI may be determined, for example, by calculation based on the solubility of PMA and phMI at the temperature at which filter filtration is performed (filtration temperature) and the amounts of phMI and organic solvent used, or by measuring the amounts of PMA and phMI dissolved in the liquid phase of the organic solvent in which phMI is dissolved by nuclear magnetic resonance (NMR).

[0144] The time for mixing the mixture of phMI and the organic solvent is not particularly limited, but from the viewpoint of stabilizing the mass ratio of PMA to phMI (PMA / phMI) and improving the PMA reduction efficiency, it is preferably 5 minutes or more, more preferably 10 minutes or more, and particularly preferably 15 minutes or more.

[0145] The temperature at which filter filtration is performed (filtration temperature) is not particularly limited, but from the viewpoint of increasing the difference in solubility between the solubility of PMA and APSI and the solubility of phMI, the temperature is preferably 60°C or less, more preferably 40°C or less, even more preferably 25°C or less, and particularly preferably 20°C or less.

[0146] The pore size of the filter used for filtration is not particularly limited, but from the viewpoint of the efficiency with which the filter captures PMA and APSI, it is preferably 1 μm or less, more preferably 0.5 μm or less, and particularly preferably 0.2 μm or less.

[0147] In order to obtain phMI from the mixture after filtration, it is necessary to distill off the solvent, but the temperature is not particularly limited as long as it is lower than the boiling point of phMI. From the viewpoint of suppressing decomposition of phMI, the temperature is preferably 30° C. to 100° C., and particularly preferably 50° C. to 80° C. or less. The solvent can be distilled off under reduced pressure as well as under normal pressure.

[0148] The solid phMI remaining after distilling off the solvent may be dried under reduced pressure. The temperature during drying is not particularly limited, but is preferably lower than the boiling point of phMI. In particular, the temperature is preferably 30°C to 100°C, and more preferably 50°C to 80°C. The solid phMI can be dried under reduced pressure as well as under normal pressure.

[0149] By the above method, an N-phenylmaleimide containing preferably 0.1 mass % or less of N-phenylmaleamic acid (PMA) and preferably 0.01 mass % or less of 2-anilino-N-phenylsuccinimide (APSI) is obtained. As described above, the N-phenylmaleimide of the present embodiment has a very low content of these impurities, so that the copolymer obtained by using this N-phenylmaleimide compound has a low content of colored compounds derived from impurities that may be generated during polymerization, and coloring of the molded product can be reduced.

[0150] (Use of Molded Body) The molded article obtained from the pellets of this embodiment is a molded article made of a methacrylic resin composition that has low birefringence, excellent heat resistance, and improved transmittance while maintaining transparency, and therefore can be suitably used for applications such as household products, office automation equipment, audio-visual equipment, battery electrical equipment parts, lighting equipment, and optical members in automobiles, etc. Examples of optical components in household products, OA equipment, AV equipment, battery-powered electrical equipment parts, lighting equipment, and the like include light guide plates, display front panels, and touch panels used in displays of smartphones, PDAs, tablet PCs, LCD televisions, and the like, as well as lenses for smartphones and tablet PC cameras, and optical lens parts for head-mounted displays and LCD projectors, such as prism elements, waveguides, and lenses, and particularly small, thin, irregularly shaped optical lenses, optical fibers, coating materials for optical fibers, lenses, Fresnel lenses, phase plates equipped with microlens arrays, and optical cover parts. Examples of optical components in automobiles and the like include light guide plates for in-vehicle displays; in-vehicle meter panels; optical components for head-up displays such as front panels, combiners, and optical cover parts for car navigation systems; in-vehicle camera lenses, light guide rods, and the like. In addition to the above, the present invention can also be preferably used as a camera focusing screen, or as a component for a digital signage display device that transmits information to a thin display connected to a network for the purpose of publicity, advertising, etc., in places such as outdoors, in stores, public institutions, and transportation facilities. EXAMPLES

[0151] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0152] <1. Measurement of impurity content in pHMI> The pHMI in the examples and comparative examples was dissolved in acetonitrile to prepare a 4 mass % solution, and measurement was performed using the following apparatus and conditions. Measurement equipment: Thermo High-performance liquid chromatography (LC Ultra3000 LTQ XL) Measurement conditions: Column: kinetex 2.6XB C-18 5.0×2.1mm, Column temperature: 40°C, flow rate: 0.2 mL / min, injection volume: 10 μL, Detector: PMA: UV detector (wavelength: 254 nm), APSI: MS (ionization: ESI+, scan range: m / z=50-1000), Mobile phase: A 0.1% by mass formic acid aqueous solution, and B 0.1% by mass formic acid acetonitrile solution, using the gradient conditions shown in Table 1 below.

[0153] [Table 1]

[0154] <2. Measurement of polymerization conversion rate> A part of the polymerization solution in each of the examples and comparative examples was collected, and the amount of monomer remaining in the polymerization solution sample was measured by dissolving the sample in chloroform to prepare a 5% by mass solution, adding n-decane as an internal standard, and measuring the concentration of the monomer remaining in the sample using gas chromatography (Shimadzu Corporation, GC-2010) to obtain the total mass (a) of the monomer remaining in the polymerization solution. The polymerization conversion rate (%) was calculated from the total mass (a), the total mass (b) assuming that all the monomers added up to the time the sample was collected remained in the polymerization solution, and the total mass (c) of the monomers added up to the end of the polymerization process, using the formula (ba) / c×100.

[0155] <3. Analysis of structural units> 1 H-NMR measurement and 13 The structural units of the produced methacrylic resin were identified by C-NMR measurement, and their amounts were calculated. 1 H-NMR measurement and 13 The measurement conditions for C-NMR measurement are as follows: Measurement equipment: Bruker DPX-400 Measurement solvent: CDCl3 or DMSO-d6 ·Measurement temperature: 40℃ Regarding the amount of structural units (X) derived from the N-substituted maleimide monomer of the methacrylic resin contained in the pellet, 1 H-NMR measurement and 13 The structural units of the methacrylic resin contained in the pellets were identified by C-NMR measurement, and their abundance was calculated from their integral ratio.

[0156] <4. Measurement of molecular weight and molecular weight distribution> The weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resins produced in the examples and comparative examples described later were measured using the following apparatus and under the following conditions. Measurement equipment: Tosoh Corporation, gel permeation chromatography (HLC-8320GPC) Measurement conditions: Columns: 1 TSKguardcolumn SuperH-H, 2 TSKgel SuperHM-M, and 1 TSKgel SuperH2500 were connected in series. Column temperature: 40°C The developing solvent was tetrahydrofuran, the flow rate was 0.6 mL / min, and 0.1 g / L of 2,6-di-t-butyl-4-methylphenol (BHT) was added as an internal standard. Detector: RI (differential refractive index) detector, detection sensitivity: 3.0 mV / min Sample: 0.02 g of methacrylic resin or 20 mL of tetrahydrofuran solution of methacrylic resin. Injection volume: 10 μL Standard sample for calibration curve: The following ten types of polymethyl methacrylate (Polymer Laboratories; PMMA Calibration Kit MM-10) with known monodisperse weight peak molecular weights and different molecular weights were used. Weight peak molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard sample 10 850 Under the above conditions, the RI detection intensity was measured versus the elution time of the methacrylic resin. Based on the calibration curve obtained by measuring the standard samples for the calibration curve, the weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin were determined.

[0157] <5. Glass transition temperature> The glass transition temperature (Tg) (°C) of the methacrylic resin was measured in accordance with JIS-K7121. First, from a sample that had been conditioned under standard conditions (23°C, 65% RH) (left at 23°C for one week), test pieces of approximately 10 mg each were cut out at four points (four locations). Next, a differential scanning calorimeter (PerkinElmer Japan Co., Ltd., Diamond DSC) was used under the condition of a nitrogen gas flow rate of 25 mL / min, where the sample was heated from room temperature (23°C) to 200°C (first heating) at 10°C / min, held at 200°C for 5 minutes to completely melt the sample, then cooled from 200°C to 40°C at 10°C / min, held at 40°C for 5 minutes, and heated again under the above heating conditions (second heating). The intersection (midpoint glass transition temperature) of the step-like change part curve during the second heating and a straight line equidistant in the vertical direction from each baseline extension line was measured as the glass transition temperature (Tg) (°C). Four points were measured per sample, and the arithmetic average (rounded off to the nearest whole number) of the four points was taken as the measured value.

[0158] <6. Measurement of composition distribution of structural units> The methacrylic resins obtained in the examples and comparative examples were subjected to molecular weight fractionation using the following apparatus and conditions. ·Preparation device: Nippon Analytical Industry Co., Ltd., LC-908 Fractionation conditions: Column: SHODEX K-2004 Eluent: chloroform, flow rate: 3 mL / min Detector: UV detector (254 nm) Sample: 3% by weight chloroform solution Fractionation method: 3 mL of sample was injected, and fractions were collected at 1-minute intervals from elution time 18 to 43 minutes. The fractionation operation was repeated three times, and the composition ratio of structural units of samples selected from the obtained fractions was determined in accordance with the above-mentioned <3. Analysis of structural units>. In addition, the molecular weight distribution was measured in accordance with <4. Measurement of molecular weight and molecular weight distribution>, and the peak top molecular weight (Mp) was calculated from the position of the apex of the peak.

[0159] 7. Quantitative Determination of 2-Amino-N-Substituted Maleimide in Pellets The amount of 2-amino-N-substituted maleimide contained in the methacrylic resin composition pellets obtained in the Examples and Comparative Examples was quantified. Specifically, 10 g of the methacrylic resin composition pellets were dissolved in chloroform to prepare a 50 mL solution, to which 300 mL of hexane was added, and the solution-soluble matter obtained by reprecipitation was separated, and molecular weight fractionation was performed by preparative GPC under the following measurement conditions. ·Preparation device: Nippon Analytical Industry Co., Ltd., LC-7080 Fractionation conditions: Column: SHODEX K-2002.5+JAIGEL-2H Eluent: chloroform, flow rate: 3 mL / min Detector: UV detector (254, 400 nm) Sample: 3% by weight chloroform solution Fractionation method: 3 mL of sample was injected, and fractions were collected at 1-minute intervals from elution time 18 to 43 minutes. Furthermore, the fractions obtained by molecular weight fractionation using preparative GPC were quantified by LC-MS under the following measurement conditions. Note that the 2-amino-N-substituted maleimides (2-anilino-N-phenylmaleimide, 2-cyclohexylamino-N-cyclohexylmaleimide) expected to be produced in the examples and comparative examples were synthesized with reference to the synthesis method disclosed in the literature "Tetrahedron Letters, 2013, 54, 6185-6188.", and a calibration curve was created using these as standards. Measurement equipment (LC section): Thermo Fisher Scientific, Ultimate 3000 Measurement conditions: Column: Intertsil ODS-3 Mobile phase: A = water, B = acetonitrile, flow rate: 3 mL / min Gradient: As shown in Table 2, a mixture of A and B was used as the mobile phase. The mobile phase was run through the column for 35 minutes while switching the mobile phase composition at the times shown in the time (min) column. [Table 2] Column temperature: 40℃ Detector: UV detector (254, 400 nm) Measurement device (MS section): Thermo Fisher Scientific, LTQ XL Ionization: ESI+ Sample injection volume: 10 μL The content of 2-amino-N-substituted maleimide quantified by LC-MS, that is, the sum of the contents of 2-anilino-N-phenylmaleimide and 2-cyclohexylamino-N-cyclohexylmaleimide, was calculated.

[0160] <8. Pellet color YI measurement> The methacrylic resin composition pellets obtained in the examples and comparative examples were used to measure color tone using a spectrophotometer SD5000 manufactured by Nippon Denshoku Industries Co., Ltd. Specifically, the pellets were filled into a measurement cell attached to the spectrophotometer, and the reflection color tone YI was determined by reflection measurement. The reflected color tone YI was calculated from the tristimulus values ​​X, Y, and Z obtained by measurement according to JIS K7105 using the formula YI=100(1.28X-1.06Z) / Y.

[0161] <9. Measurement of pellet transmittance and pellet solution YI> Using the methacrylic resin composition pellets obtained in the examples and comparative examples, the average transmittance of the pellets and the solution YI of the pellets were calculated. Specifically, the methacrylic resin composition pellets were made into a 20 w / v% chloroform solution (i.e., a solution prepared at a ratio such that 10 g of pellets were dissolved in chloroform to make a 50 mL solution) and used as a measurement sample. Using an ultraviolet-visible spectrophotometer (Shimadzu Corporation, UV-2600i), the transmittance was measured at a measurement wavelength of 380 to 780 nm, a slit width of 2 nm, a viewing angle of 10° in a 10 cm optical path length cell, auxiliary illuminant C was used, and chloroform was used as a reference object, and the average transmittance (%) in the wavelength range of 400 to 450 nm was calculated. The pellet solution YI was calculated from the tristimulus values ​​X, Y, and Z obtained by measurement according to JIS K7373, using the formula YI=100(1.28X-1.06Z) / Y.

[0162] 10. Fluorescence quantum yield of pellets The methacrylic resin composition pellets obtained in the examples and comparative examples were pulverized to 10 μm or less using a jet mill (Nano Jetmizer NJ-50-B type, manufactured by Aisin Nano Technologies Co., Ltd.) to prepare a measurement sample. The fluorescence quantum yield of the obtained powder was measured using a spectrofluorometer (F-7000, manufactured by Hitachi High-Technologies Corporation).

[0163] <11. Preparation of Molded Body> Using the methacrylic resin composition pellets obtained in the examples and comparative examples, injection molding was performed in an injection molding machine (AUTO SHOT C Series MODEL 15A, manufactured by FANUC Corporation) using a strip mold having a side gate and a thickness of 4 mm, width of 10 mm, and length of 80 mm to obtain a strip molded piece as shown in Figure 1. First, the cylinder temperature was set to 270°C, the mold temperature to 90°C, and the cooling time to 20 or 40 seconds, and the injection pressure was varied to determine the minimum injection pressure (short shot point, SSP) at which the resin was completely filled in the mold. Next, the injection pressure was set to SSP+50 kgf / cm. 2 A rectangular molded piece was obtained by injection molding under the setting of

[0164] <12. Color Tone Measurement of Molded Products> The obtained rectangular molded pieces were measured for spectral transmittance (%) and yellowness index (YI) at wavelengths of 400 to 700 nm with a long light path of 80 mm using a long light path spectrophotometer ASA1 manufactured by Nippon Denshoku Industries Co., Ltd. 成形体 The yellowness index (YI) was measured in the same manner as the color tone of the pellets. 成形体 is calculated from the tristimulus values ​​X, Y, and Z obtained by measurement according to JIS K7105. 成形体 This was calculated using the formula: =100(1.28X-1.06Z) / Y.

[0165] [Raw materials] The raw materials used in the production examples described later are shown below. [[monomer]] Methyl methacrylate (MMA): Asahi Kasei Corporation N-Phenylmaleimide (phMI, hereafter referred to as "unpurified phMI"): manufactured by Nippon Shokubai Co., Ltd. N-Cyclohexylmaleimide (chMI): Nippon Shokubai Co., Ltd. [[Polymerization initiator]] 1,1-Di(t-butylperoxy)cyclohexane: NOF Corporation's "Perhexa C" [[Chain transfer agent]] n-Octyl mercaptan: Kao Corporation

[0166] (Production of phMI with reduced PMA and APSI content) Purified phMI with reduced contents of PMA and APSI was produced by the following method.

[0167] - N-phenylmaleimide purification process - --Method of producing purified phMI1-- 3.5 g of meta-xylene (manufactured by Mitsubishi Gas Chemical Co., Ltd., hereinafter referred to as mXy) ​​and 0.30 g of unpurified phMI were weighed and added to a 50 mL screw tube (manufactured by As One Co., Ltd., model number: No. 7) equipped with a stirrer (manufactured by As One Co., Ltd., model number: C5×15), and the mixture was stirred (150 rpm) at 18° C. for 20 minutes to dissolve the unpurified phMI in mXy, thereby obtaining a phMI suspension. Note that the amount of PMA contained in the unpurified phMI before dissolving in mXy was 1150 ppm by mass, and the amount of APSI was 44 ppm by mass. The pHMI suspension was then filtered at 60° C. using a 6 mL plastic syringe (manufactured by AS ONE Corporation, product number: 2-4031-02) equipped with a polytetrafluoroethylene (PTFE) syringe filter (13JP020AN, manufactured by Advantec Toyo Co., Ltd., pore size 0.2 μm) to obtain 3.8 g of a solution layer. The solution layer was heated to 60°C under reduced pressure of 4 kPa using an evaporator (Tokyo Rikakikai Co., Ltd., model number: N-1300E), the mXy solvent was distilled off, and the remaining yellow solid was placed in a dryer (AS ONE Corporation, model number: AVO-200SB-D) and dried under reduced pressure at 60°C for 2 hours. Finally, 0.29 g of purified phMI yellow solid was obtained. The amount of PMA contained in the obtained purified phMI was 560 ppm by mass, and the amount of APSI was 44 ppm by mass (hereinafter referred to as purified phMI1).

[0168] --Method of producing purified phMI2-- The phMI suspension was filtered at 40° C. A yellow purified phMI solid was obtained under the same conditions as those for the purified phMI1. The purified phMI contained 460 ppm PMA and 40 ppm APSI (hereinafter referred to as purified phMI2).

[0169] --Method of producing purified phMI3-- The phMI suspension was filtered at 18° C. A yellow purified phMI solid was obtained under the same conditions as those for the purified phMI1. The purified phMI contained 130 ppm PMA and 36 ppm APSI (hereinafter referred to as purified phMI3).

[0170] [Comparative Example 1] 358.6 kg of methyl methacrylate (MMA), 29.4 kg of the above unpurified pHMI, 67.7 kg of N-cyclohexylmaleimide (chMI), 0.77 kg of n-octyl mercaptan as a chain transfer agent, and 224.3 kg of meta-xylene (mXy) were weighed and placed in a 1.25 m 3 The mixture was added to a reactor and stirred to obtain a mixed monomer solution. Next, 88.0 kg of MMA, 6.3 kg of unrefined phMI, and 142.4 kg of mXy were weighed and added to Tank 1 with stirring to obtain a mixed monomer solution for addition. The liquid in the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and the liquid in Tank 1 was bubbled with nitrogen at a rate of 10 L / min for 30 minutes to remove dissolved oxygen. Thereafter, steam was blown into the jacket to raise the solution temperature in the reactor to 115°C, and polymerization was initiated by adding a polymerization initiator solution prepared by dissolving 0.487 kg of 1,1-di(t-butylperoxy)cyclohexane in 1.888 kg of mXy at a rate of 1.0 kg / hour while stirring at 50 rpm. During the polymerization, the solution temperature in the reactor was controlled at 115±2°C by adjusting the temperature with the jacket. Thirty minutes after the start of polymerization, the addition rate of the initiator solution was reduced to 0.5 kg / hour. In addition, starting one hour after the start of polymerization, the entire amount of the additional mixed monomer solution was added at a constant rate from Tank 1 over a period of four hours. Furthermore, the addition rate of the initiator solution was reduced to 0.25 kg / hour 3.5 hours after the start of polymerization, and the addition was stopped 5 hours after the start of polymerization. After 12 hours had elapsed since the start of polymerization, a polymer solution containing a methacrylic resin having in its main chain a structural unit (X) derived from an N-substituted maleimide monomer was obtained. The polymer solution was sampled 2 hours and 12 hours after the start of polymerization, and the polymerization conversion was analyzed from the remaining monomer concentration. The polymerization conversion after 2 hours was MMA 78.9%, phMI 77.3%, and chMI 70.4%, and after 12 hours it was MMA 97.9%, phMI 99.4%, and chMI 99.3%. Taking into account the monomers added after 2 hours from the start of polymerization, the polymerization conversion after 2 hours was converted as the consumption rate of each monomer added by the end of polymerization, and was MMA 67.2%, phMI 67.1%, and chMI 70.4%. The polymer solution was fed to a concentrator consisting of a tubular heat exchanger and a vaporizer previously heated to 250°C, and devolatilization was carried out. The degree of vacuum in the vaporizer was set to 10 to 15 Torr. The resin flowing down the vaporizer was discharged by a gear pump, extruded from a strand die, cooled with water, and pelletized to obtain methacrylic resin composition pellets. The composition of the obtained pellets was confirmed to be 81.0 mass%, 6.6 mass%, and 12.4 mass% of structural units derived from MMA, phMI, and chMI monomers, respectively. The weight average molecular weight was 108,000, and Mw / Mn was 2.04. The glass transition temperature was 134°C. In addition, the measurement results of the composition distribution of structural units are Mp: 253,000 (MMA: 81.4 mass%, phMI: 6.5 mass%, chMI: 12.1 mass%), Mp: 176,000 (MMA: 81.1 mass%, phMI: 6.6 mass%, chMI: 12.3 mass%), Mp: 111,000 (MMA: 8 0.9 mass%, phMI: 6.7 mass%, chMI: 12.4 mass%), Mp: 88,000 (MMA: 80.8 mass%, phMI: 6.7 mass%, chMI: 12.5 mass%), Mp: 48,000 (MMA: 80.4 mass%, phMI: 6.8 mass%, chMI: 12.8 mass%). The amount of 2-amino-N-substituted maleimide contained in the obtained methacrylic resin composition pellets was quantified to be 0.31 mass ppm, and the amount of 2-amino-N-substituted maleimide per structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin in the pellets was 1.6 mass ppm. In addition, the pellet color tone was measured using the obtained methacrylic resin composition pellets, and the average transmittance in the wavelength range of 400 to 450 nm was 89%, the reflected color tone YI was 6.4 (average value of two measurements), and the solution YI of the pellets was 6.2. In addition, the fluorescence quantum yield of the obtained methacrylic resin composition pellets was measured to be 0.012.

[0171] The pellets of Comparative Example 1 were injection molded into the above-mentioned rectangular molded pieces, and the color tone was measured with a long optical path of 80 mm. 成形体 was 23.7 under molding conditions of cylinder temperature 270°C, mold temperature 90°C, and cooling time 20 s, and was 24.9 under molding conditions of cylinder temperature 270°C, mold temperature 90°C, and cooling time 40 s.

[0172] [Comparative Example 2] Purified phMI was obtained under the same conditions as for the purified phMI1, except that unpurified phMI was dissolved in mXy as N-phenylmaleimide, stirred (150 rpm) at 60° C. for 20 minutes, and filtered at 60° C. The amount of PMA contained in the obtained purified phMI was 800 ppm by mass, and the amount of APSI was 48 ppm by mass (hereinafter referred to as purified phMI4). Methacrylic resin composition pellets were produced in the same manner as in Comparative Example 1, except that purified phMI4 was used.

[0173] [Comparative Example 3] As N-phenylmaleimide, APSI was added to the purified phMI1 to adjust the APSI content to 0.03 mass%, to obtain purified phMI, which contained 130 mass ppm PMA and 3,040 mass ppm APSI (hereinafter, referred to as purified phMI5). Methacrylic resin composition pellets were produced in the same manner as in Comparative Example 1, except that purified phMI5 was used.

[0174] (Production of pellets with reduced 2-amino-N-substituted maleimide content) The following simple device was prepared for irradiating the pellets with light.

[0175] -Light irradiation device- A number of blue LED chips, NCSC119BT-V1 (peak emission wavelength 445 nm) manufactured by Nichia Chemical, were mounted on a board to serve as the light source for the light irradiation device. A water-cooled heat sink was attached to the device to suppress heat generation on the light source and irradiation surface side, and a chiller was connected to this to provide a cooling mechanism. In addition, a constant current power supply IT6533D manufactured by ITECH was used as the LED driving power source. The light output of the light irradiation device manufactured with the above configuration was approximately 1.25 W / cm at a distance of 10 mm from the light source when an applied current of 20 A was applied. 2 A jack was attached inside the device so that the distance from the light source could be changed by adjusting the height. In addition, to prevent the irradiated light from directly or indirectly reaching the human eye, the device was enclosed in a case to prevent light from leaking outside.

[0176] [Example 1] As N-phenylmaleimide, purified phMI1 obtained in the above-mentioned purification step of N-phenylmaleimide was used. Methacrylic resin composition pellets were obtained under the same conditions as in Comparative Example 1. The obtained methacrylic resin composition pellets were spread in a glass container and irradiated with light for about 1.75 hours using a light irradiation device under an output condition of an applied current of 20 A, to obtain light-irradiated pellets. The accumulated light intensity at this time was 2.2 W hr / cm. 2 The distance from the light source to the pellet surface was 10 mm. The temperature of the pellet during irradiation was about 30°C. The amount of 2-amino-N-substituted maleimide contained in the obtained methacrylic resin composition pellets was quantified to be 0.12 mass ppm, and the content of 2-amino-N-substituted maleimide per structural unit (X) derived from the N-substituted maleimide monomer of the methacrylic resin in the pellets was 0.63 mass ppm. In addition, the pellet color tone was measured using the obtained methacrylic resin composition pellets, and the average transmittance in the wavelength range of 400 to 450 nm was 96%, the reflected color tone YI was 3.7 (average value of two measurements), and the solution YI of the pellets was 3.8. In addition, the fluorescence quantum yield of the obtained methacrylic resin composition pellets was measured to be 0.003.

[0177] The pellets of Example 1 were injection molded into the above-mentioned rectangular molded pieces, and the color tone was measured with a long optical path of 80 mm. 成形体 was 22.0 under molding conditions of cylinder temperature 270°C, mold temperature 90°C, and cooling time 20 s, and was 23.9 under molding conditions of cylinder temperature 270°C, mold temperature 90°C, and cooling time 40 s.

[0178] [Example 2] As N-phenylmaleimide, unpurified phMI that was not subjected to a purification process of N-phenylmaleimide was used. Methacrylic resin composition pellets were produced under the same conditions as in Comparative Example 1, and light was irradiated under the same conditions and procedures as in Example 1 to obtain light-irradiated pellets.

[0179] [Example 3] As N-phenylmaleimide, the purified phMI2 obtained in the above-mentioned purification step of N-phenylmaleimide was used. Methacrylic resin composition pellets were produced under the same conditions as in Comparative Example 1, and were irradiated with light under the same conditions and procedures as in Example 1 to obtain light-irradiated pellets.

[0180] [Example 4] As N-phenylmaleimide, the purified phMI3 obtained in the above-mentioned purification step of N-phenylmaleimide was used. Methacrylic resin composition pellets were produced under the same conditions as in Comparative Example 1, and irradiated with light under the same conditions and procedures as in Example 1 to obtain light-irradiated pellets.

[0181] [Example 5] The methacrylic resin composition pellets obtained in Example 1 were irradiated with light at a wavelength of 390 nm using a UV-LED lamp (Kessil, PR160L-390) as a light irradiation device, with an integrated light intensity of 2.2 W hr / cm 2 Other than that, light irradiation was carried out under the same conditions and procedures as in Example 1 to obtain light-irradiated pellets.

[0182] [Example 6] The methacrylic resin composition pellets obtained in Example 1 were irradiated with light at a wavelength of 365 nm at an integrated light intensity of 2.2 W hr / cm using a tabletop batch-type UV curing device (MUVBA-0.3x0.4x0.5-0038, manufactured by ITEC Systems Co., Ltd.) as the light irradiation device. 2 Other than that, light irradiation was carried out under the same conditions and procedures as in Example 1 to obtain light-irradiated pellets.

[0183] [Table 3]

[0184] (Evaluation of mechanical properties) Furthermore, ASTM standard injection molded pieces were obtained from the pellets of the comparative example data and the example data, and the mechanical properties were evaluated by measuring tensile tests and bending tests. No difference in the mechanical properties was observed whether or not light was irradiated or whether or not the raw materials were refined.

[0185] (Evaluation of thermal properties) Regarding the thermal properties of each of the pellets in the comparative example data and the example data, each pellet was heated in a nitrogen gas flow at a rate of 10°C / min using a Shimadzu TG-DTA device (product name: DTG-60A) and an aluminum krypton cell. The thermal decomposition (TGA) of each was measured, and the thermal decomposition onset temperature was compared from the tangent intersection of the TGA curve. No difference was found in the thermal decomposition onset temperature with or without light irradiation or with or without raw material purification.

[0186] The pellets of the methacrylic resin composition of this embodiment have high heat resistance, and when the pellets of the methacrylic resin composition are irradiated with light having a wavelength of 360 to 460 nm, the color tone and fluorescence intensity are improved. Furthermore, the molded article obtained by (injection) molding the pellets of the methacrylic resin composition has a highly controlled birefringence and has a high transmittance, and therefore the molded article can be suitably used for optical component applications such as light guide plates, and automotive component applications such as light guide plates for in-vehicle displays, in-vehicle meter panels, front panels of car navigation systems, combiners, optical cover parts, and other optical parts for head-up displays. [Industrial Applicability]

[0187] The pellets and molded articles of the present invention have high heat resistance, highly controlled birefringence, and excellent transparency, and therefore can be suitably used for applications such as optical components in household products, office automation equipment, audio-visual equipment, battery electrical components, lighting equipment, and automobiles. Examples of optical components in household products, OA equipment, AV equipment, battery-powered electrical equipment parts, lighting equipment, and the like include light guide plates, display front panels, and touch panels used in displays of smartphones, PDAs, tablet PCs, LCD televisions, and the like, as well as lenses for smartphones and tablet PC cameras, and optical lens parts for head-mounted displays and LCD projectors, such as prism elements, waveguides, and lenses, and particularly small, thin, irregularly shaped optical lenses, optical fibers, coating materials for optical fibers, lenses, Fresnel lenses, phase plates equipped with microlens arrays, and optical cover parts. Examples of optical components in automobiles and the like include light guide plates for in-vehicle displays; in-vehicle meter panels; optical components for head-up displays such as front panels, combiners, and optical cover parts for car navigation systems; in-vehicle camera lenses, light guide rods, and the like. In addition to the above, the present invention can also be preferably used as a camera focusing screen, or as a component for a digital signage display device that transmits information to a thin display connected to a network for the purpose of publicity, advertising, etc., in places such as outdoors, in stores, public institutions, and transportation facilities.

[0188] Furthermore, according to the present invention, by improving the color tone and fluorescence intensity of the pellets, defective pellets that were previously out of spec in terms of color tone and fluorescence intensity can be brought within the range of non-defective pellets, thereby contributing to improved yield and an expanded operating range during production. Specifically, since an increase in heat residence time during production promotes the generation of colored components and causes deterioration of color tone and fluorescence intensity, this leads to the advantage of, for example, relaxing the temperature conditions and residence time design in the devolatilization process.

Claims

1. A pellet made of a methacrylic resin composition containing a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide monomer in its main chain, the pellet containing less than 0.30 ppm by mass of 2-amino-N-substituted maleimide.

2. 2. The pellet according to claim 1, wherein the pellet has a reflection color tone YI of 10 or less.

3. 3. The pellet according to claim 1, wherein a 20 w / v % solution of the pellet in chloroform has an average transmittance of 90% or more for light having a wavelength of 400 nm to 450 nm as measured using a 10 cm optical path length cell.

4. 3. The pellet according to claim 1, wherein the fine powder of the pellet has a fluorescence quantum yield of 0.010 or less when excited with light having a wavelength of 400 nm and a half-value width of 5 nm.

5. The pellet according to claim 1 or 2, wherein the content of 2-amino-N-substituted maleimide per structural unit (X) derived from an N-substituted maleimide monomer in the methacrylic resin in the pellet (2-amino-N-substituted maleimide amount / N-substituted maleimide monomer derived structural unit (X) amount) is less than 1.5 ppm by mass.

6. The pellet according to claim 1 or 2, wherein the methacrylic resin composition contains 50% by mass or more of a methacrylic resin containing a structural unit (X) derived from an N-substituted maleimide monomer in its main chain, based on 100% by mass of the methacrylic resin composition.

7. The pellet according to claim 1 or 2, wherein the methacrylic resin contains 3% by mass or more of a structural unit (X) derived from an N-substituted maleimide monomer in the main chain, based on 100% by mass of the methacrylic resin.

8. A molded article obtained by molding the pellets according to claim 1 or 2.

9. A method for producing a molded article containing a methacrylic resin composition, comprising: A step of polymerizing a methacrylic acid ester monomer, an N-substituted maleimide monomer, and optionally other vinyl monomers copolymerizable with the methacrylic acid ester monomer to obtain a methacrylic resin, and then optionally adding an additive to obtain a methacrylic resin composition; forming the methacrylic resin composition into pellets; The pellet is irradiated with a wavelength of 360 to 460 nm and an integrated light intensity of 0.1 to 10,000 W·hr / cm 2 and a step of heating and melting the light-irradiated pellets to obtain a molten material; and a step of injection molding the molten material to obtain a molded body. The method for producing a molded body comprising the steps of:

Citation Information

Patent Citations

  • Non-birefringent optical plastic material and optical member

    JP2006308682A

  • Imide resin, resin composition for optical use, using the same, and molded article

    JP2006328330A

  • Resin composition for optical material, and optical element

    JP2008015199A

  • Methacrylic resin, methacrylic resin composition, molding, optical component, and automatic component

    JP2020063436A

  • Acrylic thermoplastic resin and molded object thereof

    WO2011149088A1